Alkylation method of aliphatic organic compounds

By using zeolite materials with BEA framework structure synthesized without using organic templates as catalysts, the problems of catalyst stability and side reactions during the alkylation of aliphatic organic compounds are solved, and a high activity and high selectivity alkylation reaction is achieved.

CN111491908BActive Publication Date: 2025-03-21BASF SE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201880082144.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-12-21
Filing Date
2018-12-20
Publication Date
2025-03-21
Estimated Expiration
2038-12-20

AI Technical Summary

Technical Problem

The prior art has problems with catalyst stability and side reactions during the alkylation of aliphatic organic compounds, especially when using solid catalysts.

Method used

The zeolite material with a BEA framework structure synthesized without using an organic template as a structural guide is used as a catalyst, and the alkylation reaction is carried out by contacting the alkylating agent and the aliphatic organic compound.

Benefits of technology

The activity of the catalyst is significantly improved, especially under the conditions of low Si:Al molar ratio, which enhances the selectivity of the reaction product and reduces the occurrence of side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention discloses a method for alkylating aliphatic organic compounds, comprising: (a) providing a catalyst comprising one or more zeolite materials having a BEA framework structure, wherein the BEA framework structure comprises YO2 and optionally comprises X2O3, wherein Y is a tetravalent element and X is a trivalent element, (b) contacting the catalyst with one or more aliphatic organic compounds in the presence of one or more alkylating agents in one or more reactors to obtain one or more alkylated organic compounds, wherein the one or more zeolite materials can be obtained by a synthesis method that does not use an organic template as a structure directing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a process for the alkylation of aliphatic organic compounds using a catalyst comprising one or more zeolitic materials having a BEA framework structure, wherein the zeolitic materials are obtainable by a synthesis process without using an organic template as structure directing agent.

[0002] introduction

[0003] Highly branched C7 and C8 alkanes exhibit excellent fuel properties and can be prepared by alkylating isobutane with propylene or butene (see Figure 1 ). On an industrial scale, this alkylation is currently based on hydrofluoric acid or sulfuric acid; to date, no solid catalysts have been found to replace the liquid acid. Although several active solid catalysts are known, stability remains a major challenge. To date, the most promising catalysts are La- and Ce-exchanged FAU-type zeolites and different H-type zeolites, among which beta zeolite shows good results. Thus, Feller, A. et al., Journal of Catalysis, 2004, Vol. 224, pp. 80-93, relate to the alkylation of isobutane with butenes on zeolites X and Y in acidic form. On the other hand, Dalla Costa, BO et al., Applied Catalysis A 2010, Vol. 385, pp. 144-152 and Corma, A. et al., Applied Catalysis A 1994, Vol. 119, pp. 83-96, respectively, relate to the alkylation of isobutane with butenes on solid catalysts based on beta zeolite. However, there remains the ongoing challenge of balancing acid strength, as too strong acid sites promote cracking, while too weak acid sites induce dimerization of olefins.

[0004] It is also known to use beta zeolite catalysts for the alkylation of aromatic organic compounds. In this regard, WO2012 / 137133A relates to the use of beta zeolite as a solid catalyst, wherein the beta zeolite is obtained by a synthesis process without the use of an organic template. In particular, although the results show that the activity of this zeolite is lower than that of commercial beta zeolite obtained by template synthesis, the selectivity for monoalkylated products is higher. In addition, with respect to the monoalkylated products, an increase in the regioselectivity compared to commercial beta zeolite is observed.

[0005] With respect to the alkylation of aliphatic organic compounds, there remains a need for improved catalysts, particularly in view of the above-mentioned problems of catalyst stability and side reactions observed with current solid catalysts.

[0006] US4992616A and US5824835A are respectively related to heterogeneous catalytic methods for the alkylation of olefins and isoparaffins. Nivarthy, GS et al., Microporous and Mesoporous Materials 2000, Vol. 35-36, pp. 75-87 relate to the alkylation of isobutane with light olefins in a reaction catalyzed by beta zeolite. On the other hand, Nivarthy, GS et al., Microporous and Mesoporous Materials 1998, Vol. 22, No. 1-3, pp. 379-399 relate to the effect of acidity on the reaction of isobutane and light olefins catalyzed by beta zeolite. Yuki Kato et al., Journal of the Japan Petroleum Institute 2013, Vol. 56, No. 5, pp. 349-355 relate to the alkylation of isobutane with 1-butene on its H form of beta zeolite.

[0007] Detailed Description

[0008] The object of the present invention is therefore to provide an improved process for the alkylation of aliphatic organic compounds. Thus, it has surprisingly been found that such processes involving the use of a catalyst comprising a zeolitic material having a BEA framework structure, in particular a beta zeolite, can be significantly improved by using a zeolitic material therein, which can be obtained by a synthesis process without the use of an organic template as a structure directing agent. In particular, it has been very surprisingly found that by using this zeolitic material, the activity of the alkylation catalyst can be increased to an extent that could not be expected when considering the activity of commercial zeolitic materials having a BEA framework structure obtained by template synthesis. Thus, as demonstrated in the experimental part of the present application, although an increase in activity can be observed with a decrease in the Si:Al molar ratio of the latter framework structure, when using a zeolitic material having a BEA framework obtained by a synthesis process without the use of an organic template, an increase in activity can be achieved, in particular at low Si:Al molar ratios of the framework structure, which greatly exceeds the trend observed for commercial zeolites having a BEA framework structure. Furthermore and even more unexpectedly, it has surprisingly been found that the selectivity of the alkylation reaction using the zeolite material having the BEA framework structure obtainable by the organotemplate-free synthesis process for the reaction product having the same number of carbon atoms as the sum of the carbon atoms of the alkylating agent and the aliphatic organic compound is significantly higher than the selectivity when using the commercial zeolite material having the BEA framework structure. In particular, as demonstrated in the experimental part of the present application, this phenomenon is not related to particularly low Si:Al molar ratios, but the same phenomenon can also be observed at higher Si:Al molar ratios.

[0009] Therefore, the present invention relates to a method for alkylating an aliphatic organic compound, comprising:

[0010] (a) providing a catalyst comprising one or more zeolite materials having a BEA framework structure, wherein the BEA framework structure comprises YO2 and optionally comprises X2O3, wherein Y is a tetravalent element and X is a trivalent element,

[0011] (b) contacting the catalyst with one or more aliphatic organic compounds in the presence of one or more alkylating agents in one or more reactors to obtain one or more alkylated organic compounds,

[0012] The one or more zeolite materials are obtainable by a synthesis method that does not use an organic template as a structure directing agent.

[0013] According to the present invention, the terms "organic template" and "organic structure directing agent" are used synonymously, wherein the term "organic template" or "organic structure directing agent" refers to any organic compound that can be added to the synthesis method for preparing the zeolite material having the BEA framework structure as a structure directing agent, preferably any organic compound containing an organic cation. In addition, the term "organic template-free" as used in the present application refers to a synthesis method that does not use an organic template as a structure directing agent, that is, it is organic template-free, wherein the term defines a synthesis method for preparing the zeolite material having the BEA framework structure, wherein in the method, the reaction mixture never contains more than 1 wt% of the organic structure directing agent based on 100 wt% of YO2 contained in the reaction mixture, preferably more than 0.5 wt%, more preferably more than 0.1 wt%, more preferably more than 0.05 wt%, more preferably more than 0.01 wt%, more preferably more than 0.005 wt% or less, more preferably more than 0.001 wt%, more preferably more than 0.0005 wt% or less, more preferably more than 0.0001 wt% of the organic structure directing agent, based on 100 wt% of YO2 contained in the reaction mixture.

[0014] According to the present invention, there is no particular restriction on the amount and / or type of zeolitic material provided as catalyst in step (a) of the process of the present invention, provided that it has a BEA framework structure and contains at least YO2, and provided that it is suitable for catalyzing the alkylation of aliphatic organic compounds as defined in the various embodiments and / or preferred embodiments of the present invention. Thus, for example, the one or more zeolitic materials may include one or more zeolites selected from the group consisting of beta zeolite, [B-Si-O]-BEA, [Ga-Si-O]-BEA, [Ti-Si-O]-BEA, Al-rich beta zeolite, CIT-6, Chernichite and pure beta silica, wherein preferably the one or more zeolitic materials include beta zeolite. Again, among the beta zeolites preferably included in the one or more zeolitic materials, there is no particular restriction on the specific type that can be used, provided that it can be obtained by a synthesis method that does not use an organic template.

[0015] However, it is further preferred according to the present invention that the one or more zeolitic materials comprised in the catalyst of the process of the present invention consist of one or more zeolitic materials having a BEA framework structure according to any specific or preferred embodiment of the present invention, wherein more preferably, the one or more zeolitic materials comprised in the catalyst of the process of the present invention consist of a beta zeolite according to any specific or preferred embodiment of the present invention. It is also further preferred according to the present invention that the catalyst of the process of the present invention consists of one or more zeolitic materials having a BEA framework structure according to any specific or preferred embodiment of the present invention, wherein more preferably, the catalyst of the process of the present invention consists of a beta zeolite according to any specific or preferred embodiment of the present invention.

[0016] Therefore, according to the present invention, preferably the one or more zeolitic materials provided as catalyst in step (a) comprises beta zeolite, wherein preferably the one or more zeolitic materials is beta zeolite, and wherein beta zeolite is more preferably used as the one or more zeolitic materials.

[0017] In principle, the one or more zeolite materials having a BEA framework structure used in the method of the present invention can be obtained by any conceivable synthesis method, provided that they can also be obtained by a method that does not use an organic template as a structure-directing agent. Preferably, the one or more zeolite materials having a BEA framework structure are obtained by a synthesis method that does not use an organic template as a structure-directing agent. For example, Xiao et al., Chem. Mater. 2008, 20 , pp. 4533-4535 and Supporting Information describe a method for synthesizing beta zeolite, wherein beta zeolite seeds are used to crystallize aluminosilicate gel. In this regard, mention may also be made of WO 2010 / 146156 A, which relates to an organic template-free synthesis of zeolite materials having a BEA framework structure, in particular of beta zeolite. On the other hand, Majano et al., Chem. Mater. 2009, 21 , pp. 4184-4191 discuss Al-rich beta zeolite materials with Si / Al ratios as low as 3.9, which can be obtained from reactions using seeds in the absence of an organic template.

[0018] According to the present invention, the one or more zeolitic materials provided as catalyst in step (a) preferably do not contain impurities of organic structure directing agents in excess of those conventionally used in the synthesis of zeolitic materials having a BEA framework structure, in particular certain tetraalkylammonium salts and / or related organic templates, such as tetraethylammonium and / or dibenzylmethylammonium salts and dibenzyl-1,4-diazabicyclo[2,2,2]octane. Such impurities may, for example, result from organic structure directing agents still present in the seeds used in the preferred synthesis process. According to the present invention, impurities of organic templates or organic structure directing agents refer to an amount of organic structure directing agents contained in the one or more zeolitic materials of 1 wt.% or less, preferably 0.5 wt.% or less, more preferably 0.1 wt.% or less, more preferably 0.05 wt.% or less, more preferably 0.01 wt.% or less, more preferably 0.005 wt.% or less, more preferably 0.001 wt.% or less, based on 100 wt.% YO2 contained in the one or more zeolitic materials.

[0019] Furthermore, it is preferred according to the present invention that the one or more zeolitic materials having a BEA framework structure are non-calcined, which means that they have not undergone a calcination step. In the sense of the present invention, a calcination step generally refers to a process involving heating the one or more zeolitic materials to a temperature above 500°C. However, it is more preferred that the non-calcined zeolitic material of the present invention refers to a material that has not been subjected to a temperature exceeding 450°C, more preferably 350°C, more preferably 300°C, more preferably 250°C, more preferably 200°C, even more preferably not exceeding 150°C. Generally, a calcination step may refer to any step that can be used to synthesize the one or more zeolitic materials having a BEA framework structure used in the method of the present invention. However, according to the present invention, a calcination step preferably refers only to a step performed after the crystallization of the one or more zeolitic materials having a BEA framework structure from one or more precursor compounds not having a BEA framework structure is completed, except for any seeds that may be used therein. According to a further preferred embodiment of the present invention, a calcination step refers only to a step for removing the organic template from the framework structure, which is usually or appropriately performed after the crystallization of the one or more zeolitic materials is completed.

[0020] Therefore, it is preferred according to the present invention that the one or more zeolitic materials provided as catalyst in step (a) of the process of the present invention are non-calcined.

[0021] In the sense of the present invention, YO2 and optionally X2O3 contained in the BEA framework structure of the one or more zeolite materials are contained therein as structure building elements, as opposed to non-framework elements, which may be present in the pores and cavities formed by the framework structure and are generally specific to zeolite materials.

[0022] According to the present invention, Y contained in the one or more zeolitic materials having a BEA framework structure represents any conceivable tetravalent element, wherein Y is one or more tetravalent elements. According to the present invention, preferred tetravalent elements include Si, Sn, Ti, Zr and Ge and combinations thereof. More preferably, Y represents Si, Ti or Zr, or any combination of the trivalent elements, even more preferably represents Si and / or Sn. According to the present invention, it is particularly preferred that Y represents Si.

[0023] Therefore, it is preferred according to the present invention that Y contained in the one or more zeolite materials provided as catalyst in step (a) is selected from Si, Sn, Ti, Zr, Ge and a combination of two or more thereof, preferably Y is Si.

[0024] According to the present invention, it is preferred that the framework of the one or more zeolite materials having a BEA structure further comprises X2O3, wherein X represents any conceivable trivalent element, wherein X is one or more trivalent elements. Preferred trivalent elements of the present invention include Al, B, In and Ga and combinations thereof. More preferably, Y represents Al, B or In or any combination of said trivalent elements; even more preferably represents Al and / or B. According to the present invention, it is particularly preferred that X represents Al.

[0025] Therefore, it is preferred according to the present invention that X optionally contained in the one or more zeolitic materials provided as catalyst in step (a) is selected from Al, B, In, Ga and combinations of two or more thereof, preferably X is Al.

[0026] According to the present invention, it is preferred that the one or more zeolite materials having a BEA framework structure provided as catalyst in step (a) also contain X2O3 in addition to YO2. In principle, for the preferred embodiment, there are no particular restrictions on the Y:X molar ratio exhibited by the one or more zeolite materials, so that in principle zeolite materials with any conceivable and achievable Y:X molar ratio can be used. Thus, for example, the one or more zeolite materials may exhibit a Y:X molar ratio of 1-100, wherein the preferred Y:X molar ratio is 2-50, more preferably 2.5-30, more preferably 3-20, more preferably 3.5-15, more preferably 3.7-10, more preferably 3.9-8, more preferably 4.1-6, even more preferably 4.3-5.5. According to a particularly preferred embodiment, the one or more zeolite materials provided as catalyst in step (a) have a Y:X molar ratio of 4.5-5.

[0027] Therefore, according to the embodiment of the present invention wherein the one or more zeolitic materials provided as catalyst in step (a) comprises X, the Y:X molar ratio is preferably 1-100, preferably 2-50, more preferably 2.5-30, more preferably 3-20, more preferably 3.5-15, more preferably 3.7-10, more preferably 3.9-8, more preferably 4.1-6, more preferably 4.3-5.5, more preferably 4.5-5.

[0028] According to the present invention, there are no particular restrictions on any other elements or compounds that may be contained in the one or more zeolite materials having a BEA framework structure contained in the catalyst of the process of the present invention. This applies to elements contained in the framework of the one or more zeolite materials, as well as non-framework elements or compounds that may be contained in the micropores of the one or more zeolite materials, including framework structure counterions contained in the micropores of the one or more zeolite materials as non-framework elements. According to the present invention, it is preferred that the one or more zeolite materials having a BEA framework structure contain H + as counterions of the framework of the one or more zeolite materials, wherein it is further preferred according to the present invention that in addition to H + In addition, the one or more zeolitic materials contain 5 wt% or less, preferably 3 wt% or less, more preferably 1 wt% or less, more preferably 0.5 wt% or less, more preferably 0.1 wt% or less, more preferably 0.05 wt% or less, more preferably 0.01 wt% or less, more preferably 0.005 wt% or less, more preferably 0.001 wt% or less of non-framework elements, based on 100 wt% YO2.

[0029] According to the one or more zeolitic materials comprised in the catalyst of the process of the present invention comprises non-framework elements or compounds, wherein preferably the non-framework elements comprise H contained in the one or more zeolitic materials as counterions + The specific and preferred embodiments of the present invention do not have any particular restrictions on the non-framework elements or compounds that may be included therein, in particular with the exception of H which is preferably included as a counter ion in the one or more zeolitic materials. +However, it is preferred according to the present invention that the one or more zeolitic materials contain 5 wt.-% or less of Na and / or K as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of Na and / or K as non-framework elements, based on 100 wt.-% YO2. Furthermore, it is preferred that the one or more zeolitic materials contain 5 wt.-% or less of Li, Na and K as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of Li, Na and K as non-framework elements, based on 100 wt.-% YO2. It is still further preferred that the one or more zeolitic materials contain 5 wt.-% or less of alkali metals as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of alkali metals as non-framework elements, based on 100 wt.-% YO2. It is further preferred that the one or more zeolitic materials contain 5 wt.-% or less of alkali metals and alkaline earth metals as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of alkali metals and alkaline earth metals as non-framework elements, based on 100 wt.-% YO2. It is further preferred that the one or more zeolitic materials contain 5 wt.-% or less of alkali metals, alkaline earth metals and transition metals as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of alkali metals, alkaline earth metals and transition metals as non-framework elements, based on 100 wt.-% YO2.It is further preferred that the one or more zeolitic materials contain 5 wt.-% or less of metal as non-framework elements, based on 100 wt.-% YO2, preferably 3 wt.-% or less, more preferably 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, more preferably 0.001 wt.-% or less of metal as non-framework elements, based on 100 wt.-% YO2.

[0030] According to the present invention, there are no particular restrictions on the crystal structure of the one or more zeolite materials provided as catalyst in step (a) of the process according to the present invention, provided that these zeolite materials show a BEA framework structure, in particular the one or more zeolite materials provide an X-ray diffraction pattern comprising reflections that are characteristic of the BEA framework structure. In the sense of the present invention, an X-ray pattern that is characteristic of the BEA framework structure refers primarily to the reflection spectrum contained in the X-ray diffraction pattern, wherein the 2θ diffraction angle is characteristic of the BEA framework structure, and wherein preferably the relative intensities of the individual reflections are also characteristic of the BEA framework structure. According to a particularly preferred embodiment of the present invention, the one or more zeolite materials having a BEA framework structure show an X-ray diffraction pattern that comprises at least the following reflections:

[0031] strength(%) Diffraction angle 2θ / °[Cu K(α1)] [9-29] [21.06-21.26] 100 [22.11-22.31] [10-30] [25.01-25.21] [8-28] [26.77-26.97] [12-32] [28.38-28.58] [27-47] [29.22-29.42] [7-27] [29.99-30.19] [9-29] [32.85-33.25] [11-31] [42.86-43.26]

[0032] Therein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern.

[0033] More preferably, the one or more zeolitic materials having a BEA framework structure exhibit an X-ray diffraction pattern comprising at least the following reflections:

[0034]

[0035]

[0036] Therein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern.

[0037] According to the present invention, it is further preferred that the one or more zeolitic materials having a BEA framework structure provided as catalyst in step (a) of the process according to the present invention exhibit an X-ray diffraction pattern comprising at least the following reflections:

[0038] strength(%) Diffraction angle 2θ / °[Cu K(α1)] [9-29] [21.06-21.26] 100 [22.11-22.31] [10-30] [25.01-25.21] [6-26] [25.54-25.74] [8-28] [26.77-26.97] [12-32] [28.38-28.58] [27-47] [29.22-29.42] [7-27] [29.99-30.19] [9-29] [32.85-33.25] [11-31] [42.86-43.26]

[0039] More preferably, the X-ray diffraction pattern comprises at least the following reflections:

[0040] strength(%) Diffraction angle 2θ / °[Cu K(α1)] [9-29] [21.11-21.21] 100 [22.16-22.26] [10-30] [25.06-25.16] [6-26] [25.59-25.69] [8-28] [26.82-26.92] [12-32] [28.43-28.53] [27-47] [29.27-29.37] [7-27] [30.04-30.14] [9-29] [33.00-33.10] [11-31] [43.01-43.11]

[0041] Therein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern.

[0042] Therefore, it is particularly preferred according to the present invention that the one or more zeolitic materials provided as catalyst in step (a) have an X-ray diffraction pattern comprising at least the following reflections:

[0043]

[0044]

[0045] wherein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern, wherein even more preferably, the X-ray diffraction pattern further comprises the following reflections:

[0046] strength(%) Diffraction angle 2θ / °[Cu K(α1)] [6-26] [25.54-25.74]

[0047] According to the present invention, there are no particular restrictions on the surface area of ​​the one or more zeolitic materials provided as catalyst in step (a) of the process according to the invention, provided that the one or more zeolitic materials having a BEA framework structure are suitable for catalyzing the alkylation of aliphatic organic compounds. Thus, with regard to the BET surface area of ​​the one or more zeolitic materials determined according to DIN 66135, preferably according to ISO 9277, these may be, for example, in the range of 200 to 700 m 2 / g, wherein the BET surface area is preferably 250-675m 2 / g, more preferably 300-650m 2 / g, more preferably 350-625m 2 / g, more preferably 400-600m 2 / g, even more preferably 450-575m 2 According to a particularly preferred embodiment, the BET surface area determined according to DIN 66135 is 500-550 m 2 / g.

[0048] According to the present invention, the one or more zeolite materials provided as catalysts in step (a) can be obtained according to and are preferably obtained according to a synthesis method for organic template-free synthesis of zeolite materials having a BEA framework structure, wherein the synthesis method comprises the following steps:

[0049] (1) preparing a mixture comprising seed crystals and one or more YO2 sources; and

[0050] (2) crystallizing the mixture;

[0051] Wherein when the BEA framework preferably comprises X2O3, the mixture of step (1) further comprises one or more X2O3 sources.

[0052] According to the preferred synthesis providing the one or more zeolitic materials in step (a), the mixture provided in step (1) and crystallized in step (2) contains no impurities exceeding the organic structure directing agents specifically used in the synthesis of the one or more zeolitic materials having a BEA framework structure, in particular specific tetraalkylammonium salts and / or related organic templates such as tetraethylammonium and / or dibenzylmethylammonium salts and dibenzyl-1,4-diazabicyclo[2,2,2]octane. Such impurities may, for example, result from organic structure directing agents still present in the seeds used in the preferred synthesis. However, the organic templates contained in the seed material may not participate in the crystallization process, since they are trapped within the seed framework and may therefore not act as structure directing agents in the sense of the present invention.

[0053] According to the invention, in step (2) of the preferred synthesis method, a zeolitic material having a BEA framework structure is crystallized. In this regard, YO2 can be provided in step (1) in any conceivable form, provided that a zeolitic material having a BEA framework structure comprising YO2 can be crystallized in step (2). Preferably, YO2 is provided as such and / or in the form of a compound comprising YO2 as a chemical moiety and / or in the form of a compound that is (partially or completely) chemically converted into YO2 in the process of the invention. In a preferred embodiment of the invention in which Y represents Si or a combination of Si with one or more other tetravalent elements, the SiO2 source provided in step (1) can be any conceivable source. Thus, for example, all types of silica and silicates can be used, preferably pyrogenic silica, silica hydrosol, reactive amorphous solid silica, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicates or disilicates, colloidal silica, pyrogenic silica, silicates or tetraalkoxysilanes, or mixtures of at least two of these compounds.

[0054] According to a preferred embodiment of this preferred synthesis method in which the mixture of step (1) comprises one or more SiO2 sources, the sources preferably comprise one or more compounds selected from silicon dioxide and silicates, preferably silicates, more preferably alkali metal silicates. Among the preferred alkali metal silicates, the one or more sources preferably comprise water glass, more preferably sodium silicate and / or potassium silicate, more preferably sodium silicate. In a particularly preferred embodiment of the present invention, the SiO2 source is sodium silicate. In addition, in the embodiment comprising silicon dioxide, fumed silicon dioxide is preferred.

[0055] According to a preferred embodiment of the present invention, in which the one or more zeolitic materials having a BEA framework structure comprise X2O3, one or more sources of X2O3 are provided in step (1) of the preferred synthesis method. In general, X2O3 can be provided in any conceivable form, provided that the zeolitic material having a BEA framework structure comprising X2O3 can be crystallized in step (2). Preferably, X2O3 is provided as such and / or in the form of a compound comprising X2O3 as a chemical moiety and / or in the form of a compound that is (partially or completely) chemically converted into X2O3 in the process of the present invention.

[0056] According to a preferred embodiment of the preferred synthesis method in which X represents Al or a combination of Al and one or more other trivalent elements, the Al2O3 source provided in step (1) may be any conceivable source. For example, any type of alumina and aluminate, an aluminum salt such as an alkali metal aluminate, an aluminum alkoxide such as aluminum triisopropoxide, or a hydrated aluminum oxide such as aluminum trihydrate, or a mixture thereof may be used. Preferably, the Al2O3 source comprises one or more compounds selected from alumina and aluminates, preferably aluminates, more preferably alkali metal aluminates. Among the preferred alkali metal aluminates, the one or more sources preferably comprise sodium aluminate and / or potassium aluminate, more preferably sodium aluminate. In a particularly preferred embodiment of the preferred synthesis method, the Al2O3 source is sodium aluminate.

[0057] In the case where the mixture of step (1) further comprises one or more X2O3 sources including one or more boron compounds, for example free boric acid and / or borate salts and / or borate esters, such as triethyl borate or trimethyl borate, may be used as starting materials.

[0058] According to this preferred synthesis method, it is particularly preferred that the mixture of step (1) comprises one or more silicates as YO2 sources and one or more aluminates as X2O3 sources, more preferably one or more alkali metal silicates and / or one or more alkali metal aluminates, even more preferably one or more water glass compounds and / or one or more alkali metal aluminates, wherein the alkali metal of the preferred embodiment preferably includes sodium and / or potassium, more preferably sodium, and wherein the alkali metal is even more preferably sodium.

[0059] In a preferred embodiment of this preferred synthesis process in which the mixture of step (1) comprises one or more X2O3 sources, the YO2:X2O3 molar ratio of the mixture may have any conceivable value, provided that a zeolitic material having a BEA framework structure comprising YO2 and X2O3 is crystallized in step (2). Typically, the molar ratio is 1-100, preferably 5-85, more preferably 10-60, more preferably 20-55, more preferably 25-50, more preferably 35-45, particularly preferably 38-42.

[0060] According to the preferred synthesis method, it is further preferred that the zeolitic material obtained and / or obtainable according to the preferred synthesis method and / or the material of the present invention itself contains one or more alkali metals M, preferably sodium and / or potassium, more preferably sodium. The alkali metal can be added at any conceivable stage of the preferred synthesis method, wherein preferably it is also added in step (1). More preferably, the entire amount of alkali metal contained in the zeolitic material with BEA framework structure is added in step (1) of the preferred synthesis method. In a particularly preferred embodiment of the preferred synthesis method, the alkali metal is partially or completely contained in the one or more YO2 and / or X2O3 sources provided in step (1), wherein preferably, the alkali metal is partially provided by other sources. According to the particularly preferred embodiment in which the one or more alkali metals M are partially provided by one or more other sources, there is no general restriction on what type of source can be used, provided that a zeolitic material with BEA framework structure is obtained, which is suitable for catalyzing the alkylation of organic compounds itself and / or after undergoing a step of at least partially replacing the one or more alkali metals M contained therein. Preferably, the one or more other sources for providing one or more of the one or more alkali metals comprise one or more alkali metal halides, and / or one or more alkali metal hydroxides, wherein the halides are preferably selected from fluorides, chlorides and bromides. According to a particularly preferred embodiment of the preferred synthesis method, the one or more other sources comprise one or more alkali metal hydroxides, preferably sodium hydroxide and / or potassium hydroxide, even more preferably sodium hydroxide.

[0061] In general, the alkali metal M can be contained in the mixture of step (1) of the preferred synthesis process in any conceivable amount, provided that a zeolitic material having a BEA framework structure is crystallized in step (2). Preferably, the molar ratio of M:YO2 in the mixture of step (1) is 0.1-2, more preferably 0.2-1.5, more preferably 0.3-1.2, more preferably 0.4-1, more preferably 0.5-0.9, more preferably 0.55-0.8, more preferably 0.6-0.75. According to a particularly preferred embodiment of the preferred synthesis process, the molar ratio of M:YO2 in the mixture of step (1) is 0.65-0.7.

[0062] According to the preferred synthesis method, it is preferred that the mixture of step (1) comprises one or more X2O3 sources and one or more alkali metals M. In general, any conceivable amounts of these components may be contained in the mixture, provided that a zeolitic material having a BEA framework structure is crystallized in step (2). Preferably, the molar ratio of YO2:X2O3:M in the mixture of step (1) is (1-100):1:(2-90), more preferably (5-85):1:(5-70), more preferably (10-60):1:(8-50), more preferably (20-55):1:(13-35), more preferably (25-50):1:(15-30), more preferably (35-45):1:(20-29), even more preferably (38-42):1:(25-28).

[0063] According to the preferred synthesis method for obtaining the one or more zeolitic materials having a BEA framework structure, the mixture provided in step (1) comprises one or more hydroxide anions OH - In general, any conceivable OH source may be used. - Source, wherein the one or more sources preferably comprise a metal hydroxide, more preferably a hydroxide of an alkali metal M, more preferably sodium hydroxide and / or potassium hydroxide, even more preferably sodium hydroxide.

[0064] In general, the OH:YO2 molar ratio of the mixture of step (1) of the preferred synthesis process may have any conceivable value, provided that a zeolitic material having a BEA framework structure is crystallized in step (2). Preferably, the molar ratio is 0.1-1, more preferably 0.4-0.65, more preferably 0.43-0.62, more preferably 0.57-0.6, even more preferably 0.55-0.61.

[0065] According to the preferred synthesis method, it is further preferred that seed crystals are provided in step (1), wherein the seed crystals include a zeolite material having a BEA framework structure. Generally, the seed crystals may include any zeolite material having a BEA framework structure, provided that the zeolite material having a BEA framework structure is crystallized in step (2). Preferably, the zeolite material having a BEA framework structure contained in the seed crystals is obtainable according to the preferred synthesis method, preferably a zeolite material obtained according to the preferred synthesis method. More preferably, the zeolite material having a BEA framework structure contained in the seed crystals is the same as the zeolite material having a BEA framework structure subsequently crystallized in step (2). Particularly preferred are seed crystals comprising β zeolite, more preferably β zeolite obtainable according to the preferred synthesis method, or preferably β zeolite obtained according to the preferred synthesis method. In a particularly preferred embodiment, the seed crystals are β zeolite crystals, preferably β zeolite crystals obtainable according to the preferred synthesis method, or preferably β zeolite crystals obtained according to the preferred synthesis method.

[0066] According to the preferred synthesis method, any suitable amount of seed crystals may be provided in the mixture of step (1), provided that the zeolite material having a BEA framework structure is crystallized in step (2). Typically, the amount of seed crystals contained in the mixture of step (1) is 0.1-50 wt%, preferably 0.5-40 wt%, more preferably 1-35 wt%, more preferably 2-25 wt%, more preferably 3-20 wt%, more preferably 5-15 wt%, even more preferably 8-12 wt%, based on 100 wt% YO2 in the one or more source YO2.

[0067] In step (1) according to this preferred synthesis method, the mixture can be prepared by any conceivable means, wherein mixing is preferably performed by agitation, preferably by stirring.

[0068] According to the preferred synthesis method, it is preferred that the mixture of step (1) further comprises a solvent. Any conceivable solvent can be used in any conceivable amount, provided that the zeolitic material having a BEA framework structure can be crystallized in step (2) of the preferred synthesis method. Preferably, the solvent comprises water, wherein the molar ratio of H2O:YO2 in the mixture is 1-100, preferably 2-60, more preferably 5-50, more preferably 7-45, more preferably 10-30, and particularly preferably 15-25. According to the preferred synthesis method, it is further preferred that the molar ratio of H2O:YO2 in the mixture is 15-45, more preferably 20-40, and even more preferably 25-35. In a particularly preferred embodiment, the solvent provided in step (1) is distilled water.

[0069] In general, the components of the mixture used to provide step (1) of the preferred synthesis method may be added in any order, provided that the zeolitic material having a BEA framework structure is crystallized from the mixture in step (2) of the preferred synthesis method. This may, for example, involve the addition of an optional solvent and optionally one or more X2O3 sources and / or one or more OH - The one or more X2O3 sources and / or the one or more OH sources are then added, wherein the seed crystals are added to the mixture only afterwards. Alternatively, the optional solvent and the optional one or more X2O3 sources and / or the one or more OH sources may be added first. - source, followed by the addition of seed crystals, wherein the one or more YO2 sources are added only thereafter.

[0070] In general, step (2) of the preferred synthesis process can be carried out in any conceivable manner, provided that the zeolitic material having a BEA framework structure is crystallized from the mixture of step (1). The mixture can be crystallized in any type of container, wherein an agitation device is optionally used, the agitation being preferably achieved by rotation and / or stirring of the container, more preferably by stirring the mixture.

[0071] According to the preferred synthesis method, the mixture is preferably heated during at least a portion of the crystallization process in step (2). In general, the mixture can be heated to any conceivable crystallization temperature, provided that a zeolitic material having a BEA framework structure crystallizes from the mixture. Preferably, the mixture is heated to a crystallization temperature of 80-200°C, more preferably 90-180°C, more preferably 95-170°C, more preferably 100-160°C, more preferably 110-150°C, even more preferably 115-145°C.

[0072] The preferred heating in step (2) of the preferred synthesis method can be carried out in any conceivable manner suitable for crystallizing the zeolitic material having a BEA framework structure. In general, the heating can be carried out at a crystallization temperature or can be varied between different temperatures. Preferably, heating is used to increase the temperature to reach the crystallization temperature, wherein for example the heating rate can be 10-100°C / hour, more preferably 20-70°C / hour, more preferably 25-60°C / hour, more preferably 30-50°C / hour, even more preferably 35-45°C / hour.

[0073] According to this preferred synthesis method, it is preferred that in step (2), the mixture of step (1) is subjected to a pressure elevated relative to normal pressure. The term "normal pressure" as used in the context of the present invention relates to a pressure of 101,325 Pa in an ideal situation. However, the pressure may vary within boundaries known to a person skilled in the art. For example, the pressure may be 95,000-106,000 Pa, or 96,000-105,000 Pa, or 97,000-104,000 Pa, or 98,000-103,000 Pa, or 99,000-102,000 Pa.

[0074] In a preferred embodiment of this preferred synthesis process in which a solvent is present in the mixture in step (1), it is furthermore preferred that the heating in step (2) is carried out under solvothermal conditions, which means that the mixture crystallizes under the autogenous pressure of the solvent used, for example by heating in an autoclave or other crystallization vessel suitable for generating solvothermal conditions. In a particularly preferred embodiment in which the solvent comprises or consists of water, preferably of distilled water, the heating in step (2) is therefore preferably carried out under hydrothermal conditions.

[0075] There is no particular limitation on the apparatus that can be used for crystallization in the preferred synthesis process, provided that the desired parameters of the crystallization process can be achieved, particularly for preferred embodiments requiring specific crystallization conditions. In preferred embodiments carried out under solvothermal conditions, any type of autoclave or cooking vessel can be used, with Teflon-lined apparatus being preferred.

[0076] Generally, the time of the crystallization process in step (2) of the preferred synthesis method is not particularly limited. In a preferred embodiment involving heating the mixture of step (1), the crystallization process is carried out for a time of 10-200 hours, more preferably 30-150 hours, more preferably 100-140 hours, and even more preferably 110-130 hours. According to the preferred synthesis method, it is further preferred that the crystallization is carried out for a time of 5-100 hours, 10-80 hours, more preferably 20-70 hours, more preferably 30-60 hours, more preferably 40-55 hours, and even more preferably 45-50 hours.

[0077] According to a preferred embodiment of this preferred synthesis process in which the mixture is heated in step (2), the heating may be carried out during the entire crystallization process or only in one or more parts thereof, provided that a zeolitic material having a BEA framework structure is crystallized. Preferably, the heating is carried out during the entire period of crystallization.

[0078] In general, the process of the preferred synthesis method may optionally include further steps for post-treatment and / or further physical and / or chemical transformation of the zeolitic material having a BEA framework structure crystallized in step (2) from the mixture provided in step (1). The crystallized material may, for example, be subjected to any order of separation and / or washing procedures, wherein the zeolitic material obtained by the crystallization in step (2) is preferably subjected to one or more separations and one or more washing procedures.

[0079] The separation of the crystallized product can be achieved by any conceivable method. Preferably, the separation of the crystallized product can be achieved by filtration, ultrafiltration, diafiltration, centrifugation and / or decantation methods, wherein the filtration method may include suction and / or filter pressing steps.

[0080] About one or more optional washing procedures, any conceivable solvent can be used. Available washing agent is, for example, water, alcohol such as methanol, ethanol or propanol, or a mixture of two or more thereof. The example of a mixture is a mixture of two or more alcohols, for example methanol and ethanol or methanol and propanol or ethanol and propanol or methanol and ethanol and propanol, or a mixture of water and one or more alcohols, for example water and methanol or water and ethanol or water and propanol or water and methanol and ethanol or water and methanol and propanol or water and ethanol and propanol or water and methanol and ethanol and propanol. Preferred water or a mixture of water and one or more alcohols, preferably water and ethanol, wherein very particularly preferably distilled water is as unique washing agent.

[0081] Preferably, the separated zeolitic material is washed until the pH of the washing agent, preferably the washing water, is between 6 and 8, preferably between 6.5 and 7.5, as measured by a standard glass electrode.

[0082] In addition, the preferred synthesis method may optionally include one or more drying steps. Generally, any conceivable drying method can be used. The drying procedure preferably includes heating and / or applying vacuum to the zeolite material with the BEA framework structure. In the envisioned embodiment of the preferred synthesis method, one or more drying steps may include spray drying, preferably with zeolite material spray granulation.

[0083] In embodiments comprising one or more drying steps, the drying temperature is preferably 25° C.-150° C., more preferably 60° C.-140° C., more preferably 70° C.-130° C., even more preferably 75° C.-125° C. The drying time is preferably 2-60 hours, more preferably 6-48 hours, even more preferably 12-24 hours.

[0084] According to the preferred synthesis method, the zeolitic material crystallized in step (2) is preferably subjected to one or more ion exchange procedures. In general, any conceivable ion exchange procedure can be carried out on the zeolitic material with all possible ionic elements and / or molecules. Preferably, as ionic elements, one or more cations and / or cationic elements are used, which preferably include one or more selected from H + and NH4 + cations and / or cationic elements, wherein more preferably the one or more cations and / or cationic elements are H + and / or NH4 + , preferably H + According to the preferred synthesis method, it is particularly preferred that the zeolite material crystallized in step (2) is firstly reacted with NH4 + Ion exchange followed by calcination to convert the ammonium cations to H + , thereby obtaining the H form of the zeolitic material crystallized in step (2).

[0085] In general, the optional washing and / or separation and / or ion exchange procedures included in the preferred synthesis method can be carried out in any conceivable order and repeated as desired.

[0086] Therefore, the preferred synthesis method optionally includes one or more of the following steps:

[0087] (3) separating the zeolitic material having a BEA framework structure, preferably by filtration, and / or

[0088] (4) washing the zeolite material having a BEA framework structure, and / or

[0089] (5) drying the zeolite material having a BEA framework structure, and / or

[0090] (6) subjecting the zeolite material having a BEA framework structure to an ion exchange procedure,

[0091] wherein steps (3) and / or (4) and / or (5) and / or (6) may be performed in any order, and

[0092] One or more of the steps are preferably repeated at least once.

[0093] Preferably, the preferred synthesis method comprises one or more steps of isolating the zeolitic material crystallized according to step (2), more preferably isolating by filtering it. According to the preferred synthesis method, it is further preferred that after the one or more separation steps, the zeolitic material is subjected to one or more drying steps, wherein more preferably the zeolitic material is subjected to one or more washing steps before the one or more drying steps. In a particularly preferred embodiment, the zeolitic material crystallized according to step (2) is subjected to one or more separation steps, followed by one or more washing steps, followed by one or more drying steps.

[0094] According to the preferred synthesis process, it is further preferred that the zeolitic material crystallized in step (2) is directly subjected to one or more drying steps, preferably spray drying and / or spray granulation, without previously isolating, washing or drying the zeolitic material. Subjecting the mixture obtained from step (2) of the preferred synthesis process directly to a spray drying or spray granulation step has the advantage of performing separation and drying in a single step.

[0095] According to this preferred synthesis method, it is further preferred that the zeolitic material obtained from the crystallization of step (2) is subjected to one or more separation steps, preferably to one or more separation steps followed by one or more washing steps, more preferably to one or more separation steps followed by one or more washing steps and then to one or more drying steps, before being subjected to one or more ion exchange procedures.

[0096] Preferably, the preferred synthesis method does not include a calcination step which usually involves heating the zeolitic material crystallized according to step (2) to a temperature above 500° C., more preferably, the preferred synthesis method for preparing a zeolitic material having a BEA framework structure and not including a calcination step refers to a synthesis method wherein the zeolitic material crystallized according to step (2) is not subjected to a temperature exceeding 450° C., more preferably 350° C., more preferably 300° C., more preferably 250° C., more preferably 200° C., even more preferably 150° C. According to the preferred synthesis method, it is particularly preferred that after step (2) of the preferred synthesis method, wherein the crystallized zeolitic material is at ambient temperature, the material is not subsequently subjected to any heating process.

[0097] Thus, according to the present invention, the one or more zeolitic materials provided as catalyst in step (a) of the process of the present invention are preferably obtainable according to, and even more preferably obtained from, one or more of the above-mentioned preferred and particularly preferred synthesis methods.

[0098] With regard to the one or more aliphatic organic compounds contacted with the catalyst in step (b) of the process of the present invention, there are no particular restrictions on the type of organic compounds that can be used as the one or more aliphatic organic compounds, provided that they can be alkylated with the one or more alkylating agents used in the step. In this respect, it should be noted that in the sense of the present invention, the one or more alkylated organic compounds obtained in step (b) include one or more alkylated organic compounds, which are the alkylation products of the reaction of one or more aliphatic organic compounds with one or more alkylating agents. Thus, in principle, the aliphatic organic compound can be any aliphatic organic compound that is capable of reacting with at least one of the one or more alkylating agents used in step (b), wherein during the reaction at least one covalent bond is formed between a carbon atom of the aliphatic organic compound and a carbon atom of one or more of the one or more alkylating agents. There are likewise no particular restrictions on the type of covalent bond formed between the aliphatic organic compound and the alkylating agent. Thus, depending on the valence of the one or more carbon atoms of the aliphatic organic compound that forms a covalent bond with a carbon atom of the one or more alkylating agents, one or more single bonds, double bonds and / or triple bonds can be formed, wherein preferably one or more single bonds and / or double bonds are formed. However, according to the process of the present invention, it is even more preferred that one or more single bonds are formed between one or more carbon atoms of the aliphatic organic compound and one or more carbon atoms of the one or more alkylating agents.

[0099] According to the process of the present invention, the one or more aliphatic organic compounds are preferably selected from optionally substituted and / or optionally cyclic and / or optionally branched C2-C 20 Hydrocarbons and mixtures of two or more thereof, preferably C2-C 16 Hydrocarbons, more preferably C2-C 16 Hydrocarbons, more preferably C2-C 14 Hydrocarbons, more preferably C2-C 12 Hydrocarbons, more preferably C2-C 10 Hydrocarbons, more preferably C2-C8 hydrocarbons, more preferably C2-C6 hydrocarbons, more preferably C3-C5 hydrocarbons, more preferably C4 hydrocarbons and mixtures thereof.

[0100] According to the process of the present invention, it is further preferred that the one or more optionally substituted and / or optionally cyclic hydrocarbons are branched, wherein preferably the one or more branched hydrocarbons have the following formula:

[0101]

[0102] Where R 1 , R 2 and R 3are independently of one another an optionally substituted and / or optionally cyclic and / or optionally branched C1-C8 alkyl group, preferably a C1-C6 alkyl group, more preferably a C1-C5 alkyl group, wherein R 1 , R 2 and R 3 are independently of one another an optionally substituted and / or optionally branched C1-C4 alkyl group, preferably a C1-C3 alkyl group, wherein R 1 , R 2 and R 3 is independently of one another an optionally substituted methyl or ethyl group, preferably an optionally substituted methyl group. Therefore, preferred according to the invention are preferably branched hydrocarbons having the formula:

[0103]

[0104] According to any of the foregoing specific and preferred embodiments, selected from optionally substituted and / or optionally cyclic C2-C 20 Hydrocarbons and mixtures of two or more thereof, preferably C2-C 16 Hydrocarbons, more preferably C2-C 16 Hydrocarbons, more preferably C2-C 14 Hydrocarbons, more preferably C2-C 12 Hydrocarbons, more preferably C2-C 10 Hydrocarbons, more preferably C2-C8 hydrocarbons, more preferably C2-C6 hydrocarbons, more preferably C3-C5 hydrocarbons, more preferably C4 hydrocarbons and mixtures thereof.

[0105] There are no particular restrictions on the functional groups that can be used to replace the one or more aliphatic organic compounds, so that in principle the one or more aliphatic organic compounds can be substituted by any suitable functional groups. Therefore, for example, the one or more aliphatic compounds can be substituted by one or more functional groups selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, thioether, sulfinyl, sulfonyl, sulfinyl, sulfonyl, thiocyanate, isothiocyanate, phosphino, phosphono and phosphate. However, it is preferred according to the present invention that the one or more functional groups that can be used to replace the one or more aliphatic organic compounds are selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile and combinations of two or more thereof, more preferably selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether and combinations of two or more thereof, more preferably selected from hydroxyl, halogen, carbonyl, alkoxy and combinations of two or more thereof, more preferably selected from hydroxyl, fluorine, chlorine, bromine, C1-C3 alkoxy and combinations of two or more thereof, more preferably selected from hydroxyl, fluorine, chlorine, C1-C2 alkoxy and combinations of two or more thereof, more preferably selected from hydroxyl, fluorine, chlorine, methoxy and combinations of two or more thereof. According to the present invention, it is particularly preferred that the one or more functional groups that can be used to replace the one or more aliphatic organic compounds are hydroxyl.

[0106] Regarding the amount of functional groups with which the one or more aliphatic organic compounds according to any specific and preferred embodiment of the present application may be substituted, the amount may be, for example, any value from 1 to 10, wherein preferably, the preferred aliphatic organic compound is substituted with 1 to 5 functional groups, more preferably with 1 to 4 functional groups, more preferably with 1 to 3 functional groups, more preferably with 1 or 2 functional groups, and even more preferably with 1 functional group.

[0107] However, it is preferred according to the present invention that the one or more aliphatic organic compounds used in the process of the present invention according to any specific and preferred embodiments of the present application are unsubstituted hydrocarbons consisting of carbon and hydrogen atoms, wherein preferably the one or more aliphatic organic compounds include isobutane, wherein more preferably the one or more aliphatic organic compounds are isobutane, wherein more preferably isobutane is used as the one or more aliphatic organic compounds.

[0108] Concerning the actual alkylation of the aliphatic organic compounds in step (b) of the process of the present invention, there are no particular restrictions on the position of alkylation of the one or more aliphatic organic compounds, provided that one or more covalent bonds are formed between carbon atoms of the one or more aliphatic organic compounds and carbon atoms of the one or more alkylating agents.

[0109] With regard to the one or more alkylating agents used in the process according to the invention, there are in principle no restrictions on the type of compounds that can be used for this purpose, provided that they can be suitably used to alkylate one or more of the one or more aliphatic organic compounds. The same applies therefore to the type of alkyl moiety contained in the alkylating agent, so that in principle any substituted or unsubstituted cyclic, linear or branched alkyl moiety may be contained therein, wherein preferred and particularly preferred functional groups that can be used to replace the alkyl moiety of the one or more alkylating agents preferably include one or more functional groups selected from those defined above with respect to the preferred aliphatic organic compounds. According to a particularly preferred embodiment of the process according to the invention, the alkyl moiety is an unsubstituted alkyl moiety, preferably a linear and unbranched alkyl moiety.

[0110] In the sense of the present invention, the term "alkyl moiety" preferably refers to a moiety contained in the alkylating agent, which during the alkylation reaction of the process according to the invention is bonded to one or more of the one or more aliphatic organic compounds. With regard to the size of the alkyl moieties contained in the one or more alkylating agents, there are again no general restrictions in this respect according to the process according to the invention, so that in principle the one or more alkylating agents may comprise any suitable alkyl moieties, provided that the alkyl moieties can be covalently bonded to one or more of the one or more aliphatic organic compounds during the alkylation reaction in step (b) of the process according to the invention. Thus, for example, the size of the substituted or unsubstituted cyclic, linear and / or branched alkyl moieties may be C1-C 22 , wherein C1-C 20 , more preferably C1-C 18 , more preferably C1-C 16 , more preferably C1-C 14 , more preferably C1-C 10 , more preferably C1-C8, more preferably C2-C6, more preferably C3-C5, wherein even more preferably the alkyl moiety is a C4 alkyl moiety.

[0111] For example, regarding the one or more alkylating agents used in step (b) of the process of the present invention, they may include one or more compounds selected from olefins, alcohols, aldehydes, alkyl halides and mixtures of two or more thereof, wherein preferably, the one or more alkylating agents include one or more compounds selected from olefins, alcohols, alkyl halides and mixtures of two or more thereof, more preferably selected from olefins, alcohols and mixtures thereof, wherein even more preferably, the one or more alkylating agents include one or more olefins.

[0112] With regard to the preferred embodiment of the present invention in which the one or more alkylating agents comprise one or more olefins, there are no particular restrictions on the olefins that can be used, provided that the one or more aliphatic organic compounds can be alkylated in step (b) of the process of the present invention. Thus, in principle, any conceivable number of double bonds may be present therein, preferably 1 to 4 double bonds are present, more preferably 1 to 3 double bonds are present, even more preferably 1 or 2 double bonds are present. According to the present invention, it is particularly preferred that the one or more alkylating agents comprise one or more olefins containing one double bond. Furthermore, with regard to the size of the olefins that the one or more alkylating agents preferably comprise, there are again no particular restrictions, provided that they are suitable for alkylating one or more of the one or more aliphatic organic compounds in step (b) of the process of the present invention. Thus, for example, the olefin may have 2-20 carbon atoms, preferably 2-18 carbon atoms, more preferably 2-16 carbon atoms, more preferably 2-14 carbon atoms, more preferably 2-12 carbon atoms, more preferably 2-10 carbon atoms, more preferably 2-8 carbon atoms, more preferably 2-6 carbon atoms, more preferably 3-5 carbon atoms, wherein even more preferably the olefin contained in the one or more alkylating agents has 4 carbon atoms. In addition, there is no particular restriction on the structure of the olefin preferably included in the one or more alkylating agents, provided that it is suitable for alkylating one or more of the one or more aliphatic organic compounds. Thus, the olefin may be linear, cyclic and / or branched, wherein a portion of the branched olefins and the linear olefins themselves may be cyclic. According to a particularly preferred embodiment, the one or more alkylating agents include one or more linear and non-branched olefins, wherein the olefin is preferably non-cyclic.

[0113] Therefore, it is preferred according to the present invention that the one or more alkylating agents comprise one or more olefins, wherein the one or more olefins preferably comprise one or more alkenes, more preferably one or more alkenes selected from the group consisting of optionally substituted and / or optionally cyclic and / or optionally branched C2-C 20 Alkenes and mixtures of two or more thereof, preferably C2-C 18 Alkenes, more preferably C2-C 16 Alkenes, more preferably C2-C 14Alkenes, more preferably C2-C 12 Alkenes, more preferably C2-C 10 Alkenes, more preferably C2-C8 alkenes, more preferably C2-C6 alkenes, more preferably C3-C5 alkenes, more preferably C4 alkenes and mixtures thereof. Furthermore, according to any of the specific and preferred embodiments of the present invention, it is preferred that the one or more alkenes contain 1 to 4 C=C double bonds, preferably 1 to 3, more preferably 1 or 2, more preferably 1 C=C double bond.

[0114] As regards the position of the one or more C=C double bonds in any particular and preferred embodiment of the present invention wherein the one or more alkylating agents comprise one or more olefins, there are no particular restrictions, such that these may in principle be contained in the one or more olefins as terminal and / or internal C=C double bonds. However, it is preferred according to the present invention that the one or more olefins contain at least one terminal C=C double bond and / or at least one internal C=C double bond, preferably at least one terminal C=C double bond.

[0115] Therefore, it is preferred according to the present invention that the one or more alkylating agents comprise one or more olefins, wherein the one or more olefins preferably comprise one or more alkenes, wherein the one or more alkenes contain at least one terminal C=C double bond and / or at least one internal C=C double bond, preferably at least one terminal C=C double bond.

[0116] Therefore, it is particularly preferred according to the present invention that the one or more alkylating agents comprise one or more olefins, wherein the one or more olefins preferably comprise one or more alkenes, wherein the one or more alkenes are selected from optionally substituted and / or optionally cyclic and / or optionally branched ethylene, propylene, butene, pentene and mixtures of two or more thereof, wherein preferably the one or more alkenes comprise optionally substituted and / or optionally branched propylene and / or butene, wherein more preferably the one or more alkenes comprise butene, wherein more preferably the one or more alkenes are butene, wherein more preferably butene is used as the one or more alkenes. According to particularly preferred embodiments of the present invention wherein the one or more alkylating agents comprise butene, preferably wherein butene is used as the alkylating agent in step (b) of the process of the present invention, it is further preferred that the butene is selected from but-1-ene, (2Z)-but-2-ene, (2E)-but-2-ene, 2-methylprop-1-ene and mixtures of two or more thereof, preferably from but-1-ene, (2Z)-but-2-ene, (2E)-but-2-ene and mixtures of two or more thereof, wherein more preferably the butene comprises but-1-ene, wherein more preferably the butene is but-1-ene.

[0117] There are no particular restrictions on the functional groups that may be used to replace the one or more alkene reagents, so that in principle the one or more alkenes may be substituted with any suitable functional groups. Thus, for example, the one or more alkenes may be substituted with one or more functional groups selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, thioether, sulfinyl, sulfonyl, sulfinyl, sulfonyl, thiocyanate, isothiocyanate, phosphino, phosphono and phosphate. However, it is preferred according to the present invention that the one or more functional groups which can be used to replace the one or more alkenes are selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile and combinations of two or more thereof, more preferably selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether and combinations of two or more thereof, more preferably selected from the group consisting of hydroxyl, halogen, carbonyl, alkoxy and combinations of two or more thereof, more preferably selected from the group consisting of hydroxyl, fluorine, chlorine, bromine, C1-C3 alkoxy and combinations of two or more thereof, more preferably selected from the group consisting of hydroxyl, fluorine, chlorine, C1-C2 alkoxy and combinations of two or more thereof, more preferably selected from the group consisting of hydroxyl, fluorine, chlorine, methoxy and combinations of two or more thereof. It is particularly preferred according to the present invention that the one or more functional groups which can be used to replace the one or more alkenes are hydroxyl.

[0118] Regarding the amount of functional groups that can be used to replace the one or more alkenes according to any specific and preferred embodiments of the present application, for example, the number can be any value from 1 to 10, wherein preferably, the preferred alkenes are substituted with 1 to 5 functional groups, more preferably substituted with 1 to 4 functional groups, more preferably substituted with 1 to 3 functional groups, more preferably substituted with 1 or 2 functional groups, and even more preferably substituted with 1 functional group.

[0119] However, it is preferred according to the present invention that the one or more alkenes used in the process of the present invention according to any specific and preferred embodiments of the present application are unsubstituted, wherein preferably the one or more alkylating agents consist of one or more unsubstituted alkenes.

[0120] According to certain embodiments of the present invention, the alkylating agent comprises a mixture of light olefins. According to the embodiment, there are no particular restrictions on the type and composition of such mixtures, provided that one or more of the one or more aliphatic organic compounds can be appropriately alkylated, such as mixtures of ethylene, propylene, (straight and / or branched) butenes and / or (straight and / or branched) pentenes. Such mixtures can be provided by any conceivable source, such as such mixtures can be obtained from refinery streams, such as fuel gas, gas unit tail gas such as tail gas containing ethylene and / or propylene, and naphtha cracker tail gas such as tail gas containing light olefins, such as a mixture containing ethane, ethylene, propane, propylene, isobutane, normal butane, (straight and / or branched) butenes and / or (straight and / or branched) pentane, and a refinery FCC stream containing propane and propylene.

[0121] As regards the compounds contacted in step (b) of the process of the present invention for the alkylation reaction, according to the present invention, there are no particular restrictions for selecting the one or more aliphatic organic compounds according to the one or more alkylating agents used therein, and vice versa, i.e. for selecting the one or more alkylating agents according to the one or more aliphatic organic compounds used therein, provided that one or more of the one or more alkylating agents used therein are capable of alkylating one or more of the one or more aliphatic organic compounds in the presence of a catalyst comprising the one or more zeolitic materials. According to the process of the present invention, it is particularly preferred that the one or more aliphatic organic compounds comprise one or more branched hydrocarbons having the formula:

[0122]

[0123] Where R 1 , R 2 and R 3 are independently of one another an optionally substituted and / or optionally branched C1-C4 alkyl group, and the one or more alkylating agents comprise one or more alkenes selected from optionally substituted and / or optionally cyclic and / or optionally branched C2-C6 alkenes and mixtures thereof. According to the process of the present invention, it is further preferred that the one or more aliphatic organic compounds comprise one or more branched hydrocarbons having the formula:

[0124]

[0125] Where R 1 , R 2 and R 3are independently of one another an optionally substituted and / or optionally branched C1-C3 alkyl group, and the one or more alkylating agents comprise one or more alkenes selected from optionally substituted and / or optionally cyclic and / or optionally branched C3-C5 alkenes and mixtures thereof. According to the process of the present invention, it is further preferred that the one or more aliphatic organic compounds comprise one or more branched hydrocarbons having the formula:

[0126]

[0127] Where R 1 , R 2 and R 3 Independently of each other is optionally substituted methyl or ethyl, preferably optionally substituted methyl, and the one or more alkylating agents include C4 alkenes and mixtures thereof.

[0128] With regard to the alkylation reaction carried out in step (b) of the process of the present invention, according to the present invention, there are no particular restrictions on the respective amounts and proportions of the one or more aliphatic organic compounds and the one or more alkylating agents that can be used therein, nor on the reaction conditions and parameters, provided that these conditions and parameters are suitable for allowing one or more of the one or more aliphatic organic compounds to react with one or more of the one or more alkylating agents in the presence of a catalyst comprising the one or more zeolite materials. Thus, with regard to the temperatures used in one or more of the one or more reactors in step (b), these temperatures may, for example, be any temperature of 50-250° C. In the case where two or more reactors are used in step (b), the temperatures used in each reactor may be the same or may be different from each other. According to a preferred embodiment, the temperature used in one or more of the one or more reactors is 60-200° C., more preferably 70-150° C., even more preferably 80-120° C. According to a particularly preferred embodiment, the temperature used in one or more of the one or more reactors is 90-110° C.

[0129] Therefore, according to the process of the present invention, preferably step (b) is carried out at a temperature of 50-250°C, preferably 60-200°C, more preferably 70-150°C, more preferably 80-120°C, even more preferably 90-110°C.

[0130] Furthermore, with regard to the pressure at which the alkylation reaction is carried out in step (b) of the process of the present invention, there are no particular restrictions in this regard, provided that the pressure used in the one or more reactors is suitable for carrying out the alkylation. With regard to temperature, in the case where two or more reactors are used, the pressures used in the reactors may be the same or different. Thus, for example, the pressure in one or more of the one or more reactors may be any value from 1 to 50 bar, wherein preferably the pressure in the one or more reactors is 4 to 40 bar, more preferably 8 to 35 bar, more preferably 12 to 30 bar, more preferably 14 to 29 bar, more preferably 16 to 28 bar, more preferably 18 to 27 bar, more preferably 20 to 26 bar, wherein even more preferably the pressure in the one or more reactors is 22 to 25 bar.

[0131] Therefore, according to the process of the present invention, preferably step (b) is carried out at a pressure of 1-50 bar, preferably 4-40 bar, more preferably 8-35 bar, more preferably 12-30 bar, more preferably 14-29 bar, more preferably 16-28 bar, more preferably 18-27 bar, more preferably 20-26 bar, even more preferably 22-25 bar.

[0132] According to the process of the invention, the alkylation reaction is generally carried out in such a way that the organic reactants, i.e. the one or more aliphatic organic compounds and the one or more alkylating agents, are contacted with an alkylation catalyst in a suitable reaction zone, for example in one or more of one or more corresponding reactors. In this respect, there are no general restrictions on the reaction mode, provided that it is suitable for obtaining one or more alkylated compounds. Thus, the process of the invention can in principle be carried out as a batch reaction, or as a continuous process, or as a combination of a batch reaction and a continuous process, wherein it is preferably carried out as a continuous process.

[0133] Therefore, it is preferred according to the present invention that the alkylation process is carried out in batch or continuous mode, preferably in continuous mode.

[0134] According to a preferred embodiment of the present invention, in which the process of the present invention is carried out as a batch reaction, there are no particular restrictions on the reaction time used, apart from any preferred and particularly preferred reaction parameters described above and below, provided that one or more alkylated organic compounds are obtained in step (b). Thus, for example, the time of the batch reaction may be 0.5-100 hours, wherein preferably, the batch reaction is carried out for a time of 1-80 hours, more preferably 4-50 hours, more preferably 8-35 hours, more preferably 12-30 hours, more preferably 15-26 hours, even more preferably 18-22 hours.

[0135] Therefore, according to the present invention, and preferably according to a further preferred embodiment in which the process according to the invention is carried out as a batch reaction, preferably step (b) is carried out for a period of 0.5-100 hours, preferably 1-80 hours, more preferably 4-50 hours, more preferably 8-35 hours, more preferably 12-30 hours, more preferably 15-26 hours, even more preferably 18-22 hours.

[0136] It is further preferred according to the present invention that the process of the present invention is carried out in a continuous mode. According to the further preferred embodiment, there are no particular restrictions on the state of the catalyst comprising the one or more zeolite materials, so that, for example, fixed bed or fluidized bed technology can be used, and in addition a combination of fixed bed and fluidized bed technology can also be used, wherein in the case of using both fixed bed and fluidized bed technology, preferably two or more reactors are used in step (b), wherein the fixed bed and fluidized bed technology are preferably limited to separate reactors, respectively. However, according to a particularly preferred embodiment using a continuous mode, preferably in one or more of the one or more reactors, the catalyst of the process of the present invention is kept as a fixed bed.

[0137] Furthermore, according to a further preferred embodiment of the present invention wherein the process of the present invention is carried out as a continuous reaction, apart from any preferred and particularly preferred reaction parameters described hereinbefore and hereinafter, there are no particular restrictions on the feed weight hourly space velocity (WHSV) used in one or more of the one or more reactors used in the continuous process, provided that one or more alkylated organic compounds can be obtained in step (b). Thus, for example, the WHSV used in one or more of the one or more reactors may be in the range of 0.1 to 500 h -1 , where WHSV is preferably 0.5-100h -1 , more preferably 0.1-20h -1 , even more preferably 1-6h -1 .

[0138] Therefore, it is preferred according to the invention that step (b) of the process according to the invention is carried out as a continuous process.

[0139] Furthermore, it is further preferred according to the present invention that the one or more reactors used in step (b) contain a catalyst in the form of a fixed bed and / or a fluidized bed, wherein preferably one or more of the one or more reactors contain a catalyst in the form of a fixed bed.

[0140] Thus, various types of reactors may be used in the process of the present invention. For example, the process may be conducted in a batch mode, comprising adding the catalyst and aliphatic organic compound feedstock to a stirred autoclave, heating to a suitable reaction temperature, and then adding the alkylating agent feedstock. A heat transfer fluid may be circulated through the jacket of the autoclave, or a condenser may be provided to remove the heat of reaction and maintain a constant temperature. The process may also be conducted in a catalytic distillation mode.

[0141] In addition, for example, for large-scale industrial processes, fixed bed reactors operating in an upflow or downflow mode or moving bed reactors operating in co-current or countercurrent catalyst and hydrocarbon streams may be used. These reactors may contain a single catalyst bed or multiple catalyst beds and may be equipped for interstage addition of the one or more alkylating agents and interstage cooling. Interstage addition of the one or more alkylating agents and / or isothermal operation may be used to improve product quality and catalyst life. In addition, moving bed reactors may be used to continuously remove spent catalyst for regeneration and replacement with fresh or regenerated catalyst.

[0142] Regarding the ratio of the one or more aliphatic organic compounds and the one or more alkylating agents used, there are no particular restrictions according to the present invention, provided that one or more alkylated organic compounds are obtained in step (b). According to the process of the present invention, it is preferred to use at least equimolar amounts of the one or more aliphatic organic compounds and the one or more alkylating agents, wherein preferably a molar excess of the one or more aliphatic organic compounds is used relative to the amount of the one or more alkylating agents. Thus, for example, according to the process of the present invention, it is preferred that the molar ratio of the one or more aliphatic organic compounds to the one or more alkylating agents is 10-250, preferably 20-150. According to a particularly preferred embodiment, the molar ratio is 30-100, more preferably 35-80, more preferably 40-60, even more preferably 45-55.

[0143] Therefore, it is preferred according to the present invention that the molar ratio of the one or more aliphatic organic compounds to the one or more alkylating agents used in step (b) is 10-250, preferably 20-150, more preferably 30-100, more preferably 35-80, more preferably 40-60, even more preferably 45-55.

[0144] According to the present invention, the catalyst provided in step (a) can in principle be used in any suitable form, provided that it is capable of catalyzing the alkylation reaction. Thus, the alkylation catalyst provided in step (a) comprising one or more zeolite materials having a BEA framework structure can be used as such, for example in the form of a powder, a spray powder or a spray granule.

[0145] However, when the process of the invention is used on an industrial scale, preference is given to using not an alkylation catalyst in the form of a powdered or sprayed material, but an alkylation catalyst which comprises a zeolitic material in the form of a molding.

[0146] According to the process of the invention, therefore, the catalyst comprising one or more zeolitic materials having a BEA framework structure is preferably provided in the form of a molding.

[0147] Typically, the powder or spray material can be shaped in the absence of any other compounds to form a molding, for example by suitable pressing, so as to obtain a molding of the desired geometry, for example in the form of tablets, cylinders and / or spheres. However, the molding may also contain all conceivable other compounds in addition to the one or more zeolitic materials contained in the catalyst, provided that it is ensured that the resulting molding is able to catalyze the alkylation reaction in step (b). According to the preferred embodiment, it is further preferred that at least one suitable binder material is used in the preparation of the molding. In the context of this preferred embodiment, a mixture of a catalyst comprising one or more zeolitic materials and the one or more binders is more preferably prepared. Suitable binders are generally all compounds that impart bonding and / or cohesion between the one or more zeolitic materials to be bonded, in particular outside of the physical adsorption that may exist in the absence of a binder. Examples of such binders are metal oxides, such as SiO2, Al2O3, TiO2, ZrO2 or MgO, or clays or mixtures of two or more of these compounds. As Al2O3 binders, clay minerals and natural or synthetic aluminum oxides are particularly preferred, for example α-, β-, γ-, δ-, η-, κ-, χ- or θ-alumina and their inorganic or organometallic precursor compounds, for example gibbsite, bayerite, boehmite, pseudoboehmite or trialkoxyaluminates, for example aluminum triisopropoxide is particularly preferred. Further preferred binders are amphiphilic compounds with polar and nonpolar moieties and graphite. Other binders are, for example, clays, for example montmorillonite, kaolin, bentonite, halloysite, dickite, nacrite or anaxite.

[0148] According to the present invention, the adhesive can be used as is for the preparation of the molded article. However, in the context of the present invention, compounds that form the adhesive in at least one additional step of the preparation of the molded article can also be used. Examples of the adhesive precursor are tetraalkoxysilanes, tetraalkoxy titanates, tetraalkoxy zirconates, or mixtures of two or more different tetraalkoxy silanes, or mixtures of two or more different tetraalkoxy titanates, or mixtures of two or more different tetraalkoxy zirconates, or mixtures of at least one tetraalkoxy silane and at least one tetraalkoxy titanate, or mixtures of at least one tetraalkoxy titanate and at least one tetraalkoxy zirconate, or mixtures of at least one tetraalkoxy silane and at least one tetraalkoxy titanate and at least one tetraalkoxy zirconate. In the context of the present invention, it is to be mentioned that it is entirely or partially composed of SiO2 or is an adhesive precursor of SiO2, and SiO2 is formed by the precursor in at least one additional step in the preparation of the molded article. In this context, colloidal silica and "wet process" silica as well as "dry process" silica can be used. These are very particularly preferably amorphous silicon dioxide, the size of the silicon dioxide particles being, for example, 5 to 100 nm and the surface area of ​​the silicon dioxide particles being 50 to 500 m 2 / g. Colloidal silica, preferably in the form of alkaline and / or ammoniacal solution, more preferably in the form of ammoniacal solution, is commercially available, for example, especially as or "Wet process" silica is commercially available, for example, especially as or "Dry process" silica is commercially available, for example, especially as or The binder is preferably used in such an amount that the binder content of the molding finally obtained is up to 80% by weight, more preferably 5 to 80% by weight, more preferably 10 to 70% by weight, more preferably 10 to 60% by weight, more preferably 15 to 50% by weight, more preferably 15 to 45% by weight and particularly preferably 15 to 40% by weight, in each case based on the total weight of the molding finally obtained.

[0149] In principle, the molding comprising the alkylation catalyst of the present invention can be obtained according to any suitable procedure, provided that the molding can catalyze the alkylation in step (b) of the process of the present invention. According to a preferred embodiment of the present invention, the molding is obtainable according to a molding preparation method comprising the following steps, preferably according to a molding preparation method comprising the following steps:

[0150] (I) preparing a mixture comprising an alkylation catalyst and optionally at least one binder, wherein the alkylation catalyst comprises the one or more zeolite materials;

[0151] (II) optionally kneading the mixture;

[0152] (III) molding the kneaded mixture to obtain at least one molded article;

[0153] (IV) optionally drying the at least one molded article; and / or

[0154] (V) optionally calcining the at least one dried molding.

[0155] The term "finally obtained molding" as used in the context of the present invention relates to the molding obtainable from the optional drying and / or calcination step (IV) and / or (V), preferably the molding obtainable from the optional drying and / or calcination step (IV) and / or (V), particularly preferably the molding obtainable from step (IV), preferably the molding obtainable from step (IV).

[0156] Thus, a mixture of a binder or binder precursor and a catalyst comprising one or more zeolite materials can be mixed with at least one other compound for further processing and forming a plastic material. Here, pore formers can be particularly preferably mentioned. In the method of the present invention, all compounds that provide a certain pore size and / or a certain pore size distribution and / or a certain pore volume for the final molded product can be used as pore formers. Pore formers preferably used in the method of the present invention are polymers that are dispersible, suspendable or emulsifiable in water or in an aqueous solvent mixture. Preferred polymers here are polymeric vinyl compounds, such as polyoxyalkylenes such as polyethylene oxide, polystyrene, polyacrylates, polymethacrylates, polyolefins, polyamides and polyesters, carbohydrates such as cellulose or cellulose derivatives, such as methylcellulose, or sugars or natural fibers. Other suitable pore formers are, for example, pulp or graphite. If a pore former is used in the preparation of a mixture according to (I), the pore former content of the mixture according to (I), preferably the polymer content is preferably 5-90% by weight, preferably 15-75% by weight, particularly preferably 25-55% by weight, in each case based on the amount of the one or more zeolite materials in the mixture according to (I). If it is desired to achieve a pore size distribution, a mixture of two or more pore formers can also be used. In a preferred embodiment of the process according to the invention, the pore former is removed by calcination in step (V), thereby obtaining a porous molding. However, it is particularly preferred according to the invention that the molding obtained in step (III) is not subsequently subjected to a calcination step. With regard to the calcination of the molding preferably used in the process according to the invention, the term "calcination" refers to a calcination step as defined above for the one or more zeolitic materials. Therefore, according to a particularly preferred embodiment of the present invention in which the molding obtained in step (III) is not subsequently subjected to a calcination step, it is therefore preferred according to said embodiment to use no pore former, or to use one or more pore formers that can be suitably removed by a heating step other than a calcination step in the sense of the present invention, and / or can be removed by other means than suitably heating the preferred molding containing one or more pore formers.

[0157] In the context of an equally preferred embodiment of the present invention, at least one gelling agent is added during the preparation of the mixture according to (I). Useful gelling agents are all compounds suitable for this purpose. These are preferably organic, in particular hydrophilic polymers, for example cellulose, cellulose derivatives such as methylcellulose, starches such as potato starch, wallpaper paste, polyacrylates, polymethacrylates, polyvinyl alcohol, polyvinyl pyrrolidone, polyisobutylene or polytetrahydrofuran. Therefore, specific compounds that are pore formers can also be used as gelling agents. In a particularly preferred embodiment of the process of the present invention as described below, these gelling agents are removed by calcination in step (V) to obtain a porous molding. However, it is particularly preferred according to the present invention that the molding obtained in step (III) is not subsequently subjected to a calcination step. Therefore, according to a particularly preferred embodiment of the present invention in which a calcination step is not applied to the molding obtained in step (III), it is therefore preferred according to said embodiment that no gelling agent is used, or one or more gelling agents that can be suitably removed by a heating step other than a calcination step in the sense of the present invention are used, and / or can be removed by other means other than suitably heating the preferred molding containing one or more gelling agents.

[0158] According to another embodiment of the present invention, at least one acidic additive can be added during the preparation of the mixture according to (I). In this respect, it is preferred that the organic acidic compound can be removed in the optional calcining step (V). Particularly preferred are carboxylic acids, such as formic acid, oxalic acid and / or citric acid. Two or more of these acidic compounds can also be used. However, about the above-mentioned pore former and pasting agent, it is preferred to use one or more acidic additives and preferably one or more organic acidic compounds, which can be removed by a heating step rather than a calcining step in the sense of the present invention, and / or can be removed by other means except suitable heating containing one or more acidic additives, preferably one or more organic acidic compounds preferred moldings.

[0159] The order of adding the components of the mixture according to (I) comprising the alkylation catalyst containing the one or more zeolite materials having a BEA framework structure is not critical. In particular, the at least one binder may be added first, followed by the at least one pore former and the at least one acidic compound, and finally the at least one pasting agent; the order of the at least one binder, the at least one pore former, the at least one acidic compound and the at least one pasting agent may also be interchanged.

[0160] After the addition of the binder to the alkylation catalyst comprising the zeolitic material, to which, if appropriate, at least one of the abovementioned compounds has been added, the mixture according to (I) is usually homogenized for 10 to 180 minutes. Particular preference is given to using a kneader, a wheel mill or an extruder for the homogenization. The mixture is preferably kneaded. On an industrial scale, the homogenization is preferably carried out using a wheel mill process. The homogenization is usually carried out at a temperature of about 10° C. to the boiling point of the pasting agent and at atmospheric pressure or slightly superatmospheric pressure. Subsequently, if appropriate, at least one of the abovementioned compounds can be added. The mixture thus obtained is homogenized, preferably kneaded, until an extrudable plastic material is formed.

[0161] According to the preferred method for producing the moldings according to the invention, the homogenized mixture is subsequently molded. In the context of the present invention, preference is given to molding methods in which molding is carried out by extrusion in conventional extruders, for example to give extrudates with a diameter of preferably 1 to 10 mm, particularly preferably 2 to 5 mm. Such extrusion devices are described, for example, in Ullmann's der Technischen Chemie, 4th edition, volume 2, pages 295 ff., 1972. In addition to the use of screw-type extruders, it is also preferred to use plunger-type extruders for molding. In principle, however, all known and / or suitable kneading and molding devices and methods can be used for shaping. Examples of these are, in particular: briquetting, i.e. mechanical compression with or without the addition of further binder materials; granulation, i.e. compacting by circular and / or rotary movements; sintering, i.e. subjecting the material to be molded to a heat treatment. The shape of the moldings produced according to the invention can be selected as desired. In particular, spherical, elliptical, cylindrical or lamellar shapes are particularly possible.

[0162] In the context of the present invention, at least one drying step is preferably carried out after step (III). In principle, any suitable drying step can be used, provided that a dry molding is provided. However, it is preferred according to the invention that the drying step does not involve the temperatures used in the calcination step in the sense of the present invention.

[0163] In the context of the present invention, after the optional drying step (IV), at least one calcination step (V) is optionally carried out. According to certain embodiments, the calcination step (V) is carried out directly after the molding step (III). However, it is preferred according to the present invention that after the optional drying step (IV), the preferred molding comprising the alkylation catalyst comprising the one or more zeolitic materials having a BEA framework structure is not subjected to a calcination step (V), wherein according to said particularly preferred embodiments not comprising a calcination step (V), it is preferred that the preparation process comprises one or more drying steps (IV) carried out after the molding step (III).

[0164] According to the embodiment in which the preferred moldings are obtainable according to the above-mentioned preferred molding preparation process comprising one or more calcination steps (V), preferably according to the method, the calcination can generally be carried out at any temperature defined in the sense of the present invention, wherein preferably at a temperature of 300-700° C., more preferably 400-600° C. is carried out. According to said embodiment, the calcination can be carried out under any suitable gas atmosphere, preferably air and / or lean air. Furthermore, the calcination is preferably carried out in a muffle furnace, a rotary kiln and / or a belt calciner. The temperature during the calcination step can be kept constant or varied continuously or discontinuously. If the calcination is carried out two or more times, the calcination temperatures in the individual steps may be different or the same.

[0165] Before and / or after the optional drying step (IV) and / or before and / or after the optional calcination step (V), if appropriate, the at least one molding can be treated with a concentrated or dilute Bronsted acid or a mixture of two or more Bronsted acids. Suitable acids are, for example, hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid or carboxylic acids, dicarboxylic acids or oligo- or polycarboxylic acids, such as nitrilotriacetic acid, sulfosalicylic acid or ethylenediaminetetraacetic acid. If appropriate, after this at least one treatment with at least one Bronsted acid, at least one drying step (IV) and / or at least one calcination step (V) is carried out.

[0166] According to a further embodiment of the process according to the invention, the molding preferably provided in step (a) and used in step (b) can be subjected to a steam treatment for better hardening, preferably followed by at least one further drying and / or at least one further calcination. For example, after at least one drying step and at least one subsequent calcination step, the calcined molding is subjected to a steam treatment and then subjected to at least one further drying and / or at least one further calcination.

[0167] The present invention is further illustrated by the following embodiment sets and embodiment combinations resulting from the indicated references and back references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of a term such as "a method according to any one of embodiments 1-4", it is meant that each embodiment in the range is clearly disclosed to a person skilled in the art, i.e. the wording of the term should be understood by a skilled person as being synonymous with "a method according to any one of embodiments 1, 2, 3 and 4".

[0168] 1. A method for alkylating an aliphatic organic compound, comprising:

[0169] (a) providing a catalyst comprising one or more zeolite materials having a BEA framework structure, wherein the BEA framework structure comprises YO2 and optionally comprises X2O3, wherein Y is a tetravalent element and X is a trivalent element,

[0170] (b) contacting the catalyst with one or more aliphatic organic compounds in the presence of one or more alkylating agents in one or more reactors to obtain one or more alkylated organic compounds,

[0171] The one or more zeolite materials are obtainable by a synthesis method that does not use an organic template as a structure directing agent.

[0172] 2. The process according to embodiment 1, wherein the one or more zeolitic materials are non-calcined.

[0173] 3. The method according to embodiment 1 or 2, wherein Y is selected from Si, Sn, Ti, Zr, Ge and combinations of two or more thereof, preferably Y is Si.

[0174] 4. The method according to any one of embodiments 1 to 3, wherein X is selected from Al, B, In, Ga and combinations of two or more thereof, preferably X is Al.

[0175] 5. The process according to any one of embodiments 1 to 4, wherein one or more of the one or more zeolitic materials has a Y:X molar ratio of 1-100, preferably 2-50, more preferably 2.5-30, more preferably 3-20, more preferably 3.5-15, more preferably 3.7-10, more preferably 3.9-8, more preferably 4.1-6, more preferably 4.3-5.5, more preferably 4.5-5.

[0176] 6. The method according to any one of embodiments 1 to 5, wherein the one or more zeolite materials comprise H + As counterions of the framework of the one or more zeolite materials, wherein preferably, in addition to H + In addition, the one or more zeolite materials further comprise 5 wt% or less, preferably 3 wt% or less, more preferably 1 wt% or less, more preferably 0.5 wt% or less, more preferably 0.1 wt% or less, more preferably 0.05 wt% or less, more preferably 0.01 wt% or less, more preferably 0.005 wt% or less, more preferably 0.001 wt% or less of non-framework elements, based on 100 wt% YO2.

[0177] 7. A method according to embodiment 6, wherein the non-framework elements are Na and / or K as non-framework elements, preferably Li, Na and K as non-framework elements, more preferably alkali metals as non-framework elements, more preferably alkali metals and alkaline earth metals as non-framework elements, more preferably alkali metals, alkaline earth metals and transition metals as non-framework elements, more preferably metals as non-framework elements.

[0178] 8. The method according to any one of embodiments 1 to 7, wherein one or more of the one or more zeolitic materials has an X-ray diffraction pattern comprising at least the following reflections:

[0179]

[0180]

[0181] Therein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern.

[0182] 9. The method according to embodiment 8, wherein the X-ray diffraction pattern further comprises the following reflections:

[0183] strength(%) Diffraction angle 2θ / °[Cu K(α1)] [6-26] [25.54-25.74]

[0184] 10. The process according to any one of embodiments 1 to 9, wherein one or more of the one or more zeolitic materials has a BET surface area of ​​200 to 700 m2 as determined according to ISO 9277. 2 / g, preferably 250-675m 2 / g, more preferably 300-650m 2 / g, more preferably 350-625m 2 / g, more preferably 400-600m 2 / g, more preferably 450-575m 2 / g, even more preferably 500-550m 2 / g.

[0185] 11. The method according to any of embodiments 1 to 10, wherein the one or more zeolite materials comprises beta zeolite, preferably wherein the one or more zeolite materials is beta zeolite, wherein beta zeolite is more preferably used as the one or more zeolite materials.

[0186] 12. The method according to any one of embodiments 1 to 11, wherein the one or more aliphatic organic compounds are selected from optionally substituted and / or optionally cyclic and / or optionally branched C2-C 20 Hydrocarbons and mixtures of two or more thereof, preferably C2-C 16 Hydrocarbons, more preferably C2-C 16 Hydrocarbons, more preferably C2-C 14 Hydrocarbons, more preferably C2-C 12 Hydrocarbons, more preferably C2-C 10 Hydrocarbons, more preferably C2-C8 hydrocarbons, more preferably C2-C6 hydrocarbons, more preferably C3-C5 hydrocarbons, more preferably C4 hydrocarbons and mixtures thereof

[0187] 13. The process according to embodiment 12, wherein the one or more optionally substituted and / or optionally cyclic hydrocarbons are branched, wherein preferably the one or more branched hydrocarbons have the following formula:

[0188]

[0189] Where R 1 , R 2 and R 3 are independently of one another an optionally substituted and / or optionally cyclic and / or optionally branched C1-C8 alkyl group, preferably a C1-C6 alkyl group, more preferably a C1-C5 alkyl group, wherein R 1 , R 2 and R 3 are independently of one another an optionally substituted and / or optionally branched C1-C4 alkyl group, preferably a C1-C3 alkyl group, wherein R 1 , R 2 and R 3 Independently of each other are optionally substituted methyl or ethyl, preferably optionally substituted methyl.

[0190] 14. The method according to embodiment 12 or 13, wherein the one or more aliphatic organic compounds are substituted by one or more functional groups, wherein the one or more functional groups are preferably selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, thioether, sulfinyl, sulfonyl, sulfinyl, sulfonyl, thiocyanate, isothiocyanate, phosphine, phosphonyl and phosphate,

[0191] More preferably, it is selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, and combinations of two or more thereof,

[0192] More preferably, it is selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, and combinations of two or more thereof,

[0193] More preferably, it is selected from hydroxyl, halogen, carbonyl, alkoxy and combinations of two or more thereof,

[0194] More preferably, it is selected from hydroxy, fluorine, chlorine, bromine, C1-C3 alkoxy and a combination of two or more thereof,

[0195] More preferably, it is selected from hydroxy, fluorine, chlorine, C1-C2 alkoxy and a combination of two or more thereof,

[0196] More preferably, it is selected from hydroxy, fluorine, chlorine, methoxy and combinations of two or more thereof,

[0197] More preferably, the one or more aliphatic compounds are substituted with one or more hydroxyl groups.

[0198] 15. The method according to embodiment 12 or 13, wherein the one or more aliphatic organic compounds are unsubstituted hydrocarbons, wherein preferably the one or more aliphatic organic compounds include isobutane, wherein more preferably the one or more aliphatic organic compounds are isobutane, wherein more preferably isobutane is used as the one or more aliphatic organic compounds.

[0199] 16. A process according to any one of embodiments 1 to 15, wherein the one or more alkylating agents comprise one or more compounds selected from the group consisting of olefins, alcohols, aldehydes, alkyl halides, and mixtures of two or more thereof, preferably selected from the group consisting of olefins, alcohols, alkyl halides, and mixtures of two or more thereof, more preferably selected from the group consisting of olefins, alcohols, and mixtures thereof, wherein even more preferably the one or more alkylating agents comprise one or more olefins.

[0200] 17. The process according to embodiment 16, wherein the olefin comprises one or more alkenes, more preferably one or more alkenes selected from the group consisting of optionally substituted and / or optionally cyclic and / or optionally branched C2-C 20 Alkenes and mixtures of two or more thereof, preferably C2-C 18 Alkenes, more preferably C2-C 16 Alkenes, more preferably C2-C 14 Alkenes, more preferably C2-C 12 Alkenes, more preferably C2-C 10 Alkenes, more preferably C2-C8 alkenes, more preferably C2-C6 alkenes, more preferably C3-C5 alkenes, more preferably C4 alkenes, and mixtures thereof.

[0201] 18. The process according to embodiment 17, wherein the one or more alkenes contain 1 to 4 C=C double bonds, preferably 1 to 3, more preferably 1 or 2, more preferably 1 C=C double bond.

[0202] 19. The process according to any of embodiments 17-18, wherein the one or more alkenes comprise at least one terminal C=C double bond and / or at least one internal C=C double bond, preferably at least one terminal C=C double bond.

[0203] 20. The method according to any one of embodiments 17-19, wherein the one or more alkenes are selected from optionally substituted and / or optionally cyclic and / or optionally branched ethylene, propylene, butene, pentene and mixtures of two or more thereof, wherein preferably the one or more alkenes include optionally substituted and / or optionally branched propylene and / or butene, wherein more preferably the one or more alkenes include butene, wherein more preferably the one or more alkenes are butene, wherein more preferably butene is used as the one or more alkenes.

[0204] 21. A method according to embodiment 20, wherein the butene is selected from but-1-ene, (2Z)-but-2-ene, (2E)-but-2-ene, 2-methylprop-1-ene and a mixture of two or more thereof, preferably selected from but-1-ene, (2Z)-but-2-ene, (2E)-but-2-ene and a mixture of two or more thereof, wherein more preferably the butene comprises but-1-ene, wherein more preferably the butene is but-1-ene.

[0205] 22. The method according to any one of embodiments 17 to 21, wherein the one or more alkene reagents are substituted by one or more functional groups, wherein the one or more functional groups are preferably selected from hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, thioether, sulfinyl, sulfonyl, sulfinyl, sulfonyl, thiocyanate, isothiocyanate, phosphino, phosphono and phosphate,

[0206] More preferably, it is selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, and combinations of two or more thereof,

[0207] More preferably, it is selected from hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, and combinations of two or more thereof,

[0208] More preferably, it is selected from hydroxyl, halogen, carbonyl, alkoxy and combinations of two or more thereof,

[0209] More preferably, it is selected from hydroxy, fluorine, chlorine, bromine, C1-C3 alkoxy and a combination of two or more thereof,

[0210] More preferably, it is selected from hydroxy, fluorine, chlorine, C1-C2 alkoxy and a combination of two or more thereof,

[0211] More preferably, it is selected from hydroxy, fluorine, chlorine, methoxy and combinations of two or more thereof,

[0212] More preferably, the one or more alkylating agents are substituted with one or more hydroxyl groups.

[0213] 23. The process according to any of embodiments 16 to 21, wherein the one or more alkenes are unsubstituted, wherein preferably the one or more alkylating agents consist of one or more unsubstituted alkenes.

[0214] 24. The method according to any one of embodiments 1 to 23, wherein the molar ratio of the one or more aliphatic organic compounds to the one or more alkylating agents is 10-250, preferably 20-150, more preferably 30-100, more preferably 35-80, more preferably 40-60, even more preferably 45-55.

[0215] 25. According to the process according to any one of embodiments 1 to 24, step (b) is carried out at a temperature of 50-250°C, preferably 60-200°C, more preferably 70-150°C, more preferably 80-120°C, even more preferably 90-110°C.

[0216] 26. The process according to any one of embodiments 1 to 25, wherein step (b) is carried out at a pressure of 1-50 bar, preferably 4-40 bar, more preferably 8-35 bar, more preferably 12-30 bar, more preferably 14-29 bar, more preferably 16-28 bar, more preferably 18-27 bar, more preferably 20-26 bar, even more preferably 22-25 bar.

[0217] 27. The method according to any one of embodiments 1-26, wherein step (b) is performed for a period of 0.5-100 hours, preferably 1-80 hours, more preferably 4-50 hours, more preferably 8-35 hours, more preferably 12-30 hours, more preferably 15-26 hours, even more preferably 18-22 hours.

[0218] 28. The process according to any of embodiments 1 to 27, wherein the process is performed in batch or continuous mode, preferably in continuous mode.

[0219] 29. The method according to any one of embodiments 1 to 28, wherein the one or more reactors contain the catalyst in the form of a fixed bed and / or a fluidized bed, wherein preferably one or more of the one or more reactors contain the catalyst in the form of a fixed bed.

[0220] 30. The process according to any of embodiments 1 to 29, wherein the catalyst comprising one or more zeolitic materials having a BEA framework structure is provided in the form of a molded article. BRIEF DESCRIPTION OF THE DRAWINGS

[0221] Figure 1 The reaction of isobutane with linear butenes and their direct reaction products are shown schematically.

[0222] Figure 2 Shown is an X-ray diffraction (XRD) pattern (measured using Cu Kα-1 radiation) of the zeolitic material obtained by organic template-free synthesis according to Reference Example 2, in which the diffraction angle 2θ in ° is shown along the abscissa and the intensity is plotted along the ordinate. Figure 2 Further included are the corresponding line plots for zeolite beta obtained by template-mediated synthesis and mordenite for comparison.

[0223] Figure 3 shows the nitrogen adsorption isotherm of the zeolite material obtained according to Reference Example 2. In this figure, the relative pressure p / p 0 Plotted along the abscissa, the measured values ​​in cm according to DIN 66134 at 77 K 3 The pore volume of the STP (standard pressure and temperature) meter is plotted along the ordinate. The adsorption value is represented by the symbol (◆) and the desorption value is represented by the symbol (▲).

[0224] Figure 4 The experimental test results of the catalyst samples of Reference Examples 2, 4, 5, 7 and 9 obtained according to Example 1 in the alkylation of isobutane with but-1-ene are shown. In this figure, the Si:Al molar ratio of each sample is plotted along the abscissa, and the alkylation product yield in mg relative to the amount of catalyst in g (mg product / g catalyst) is plotted along the ordinate. The values ​​obtained in Reference Examples 2, 4 and 5 are represented by the symbol (◆), the values ​​obtained in the dealuminated samples of Reference Examples 7 and 9 are represented by the symbol (●), and the values ​​obtained in the commercial beta zeolite sample are represented by the symbol (▲).

[0225] Figure 5 The experimental test results of the catalyst samples of Reference Examples 2, 4, 5, 7 and 9 obtained according to Example 1 in the alkylation of isobutane with but-1-ene are shown. In this figure, the Si:Al molar ratio of each sample is plotted along the abscissa, and the selectivity of each catalyst sample to C8 alkylated product is plotted along the ordinate, expressed as % relative to 100% alkylated product. The values ​​obtained in Reference Examples 2, 4 and 5 are represented by the symbol (◆), the values ​​obtained in the dealuminated samples of Reference Examples 7 and 9 are represented by the symbol (●), and the values ​​obtained in the commercial beta zeolite sample are represented by the symbol (▲).

[0226] Figure 6 Shown is an X-ray diffraction (XRD) pattern (measured using Cu Kα-1 radiation) of the zeolitic material obtained according to Reference Example 10, in which the diffraction angle 2θ in ° is shown along the abscissa and the intensity is plotted along the ordinate. Figure 6 Further included are the corresponding line plots for zeolite beta and chabazite. Example

[0227] Reference Example 1: Preparation of zeolite beta by organic template-free synthesis

[0228] 23.95 g of NaAlO2 were dissolved in 812.35 g of H2O, followed by the addition of 9.01 g of Al-β zeolite seeds (CP814C β zeolite from Zeolyst International; calcined at 500° C. for 5 hours to obtain the H form before use). Then, 1154.69 g of sodium-water glass solution (26 wt. % SiO2 and 8 wt. % Na2O, from Fa. Woellne) were slowly added to the mixture while stirring, where a gel first formed and then dissolved after further addition of solution.

[0229] Then, the mixture was transferred to a 2.5L autoclave, heated to 120°C for 3 hours without stirring, and then crystallized at this temperature for 117 hours. After the reaction mixture was cooled to room temperature, it was filtered, and the solid residue was repeatedly washed with distilled water to neutralize, followed by drying at 120°C for 16 hours, thereby obtaining 85g of a white crystalline product. Compared with the crystallinity of the seed crystal used in the synthesis, the product showed a crystallinity level of 90% in the 2θ range of 18-25°.

[0230] Figure 2 The XRD of the crystalline product is shown. In particular, the XRD pattern is characteristic of the BEA framework structure obtained by the organic template-free synthesis method, in view of the two characteristic reflections observed in the 2θ range of 25-26°.

[0231] Elemental analysis of the crystalline product gave a Si:Al molar ratio of 4.8: 1. Energy dispersive X-ray (EDX) composition analysis of the sample gave a Si:Al molar ratio of 4.9: 1.

[0232] 1 g of the crystalline product was then subjected to two successive ion exchange steps at 80° C. with a 10% by weight aqueous ammonium nitrate solution, wherein the ion-exchanged material was calcined at 350° C. for 5 hours.

[0233] Figure 3 The nitrogen isotherms obtained using the ion exchanged products are shown. In particular, the step-like curve of the type I adsorption isotherm characteristic of microporous solids is evident (see DIN 66135), which indicates that the synthesized zeolitic material has open micropores. Evaluation of the data gives a value of 681 m / s according to the Langmuir method. 2 / g equivalent surface area and 521m 2 / g of BET surface area.

[0234] Reference Example 2: Preparation of H-type β zeolite from the product of Reference Example 1

[0235] The non-ion-exchanged crystalline product of Reference Example 1 was subjected to three successive ion-exchange steps with 0.5 M ammonium nitrate solution and subsequently calcined at 450° C. for 6 hours.

[0236] Reference Example 3: Preparation of zeolite beta by organic template-free synthesis

[0237] 332.1 g NaAlO2 was dissolved in 7578.8 g H2O, followed by the addition of 62.8 g Al-β zeolite seeds (CP814C β zeolite from Zeolyst International; H type), followed by the slow addition of 363.6 g fumed silica (obtained from Degussa; 200). The mixture was then transferred to a 20 L autoclave, and 8062.6 g of sodium-water glass solution (26 wt. % SiO2 and 8 wt. % Na2O, obtained from Fa. Woelner) were then slowly added to the mixture while stirring, wherein a gel was first produced and then dissolved after further addition of solution.

[0238] Then, the mixture was heated to 120° C. for 3 hours without stirring, and then crystallized at this temperature for 117 hours. After the reaction mixture was cooled to room temperature, it was filtered, and the solid residue was repeatedly washed with distilled water to neutralize, and then dried at 120° C. for 16 hours to obtain 1330 g of a white crystalline product. Compared with the crystallinity of the seed crystals used in the synthesis, the product showed a crystallinity level of 90% in the 2θ range of 18-25°.

[0239] Elemental analysis of the crystalline product gave a Si:Al molar ratio of 4.5:1.

[0240] For Reference Example 1, considering the two characteristic reflections observed in the range of 25-26° 2θ, the XRD of the crystalline product showed an XRD pattern characteristic of the BEA framework structure obtained by organic template-free synthesis.

[0241] Reference Example 4: Preparation of H-type zeolite beta from the product of Reference Example 3

[0242] The crystalline product of Reference Example 3 was subjected to three successive ion exchange steps with 0.5 M ammonium nitrate solution and subsequently calcined at 450° C. for 6 hours.

[0243] Reference Example 5: Preparation of zeolite beta by organic template-free synthesis

[0244] 18.28 kg of Al-β zeolite seeds (CP814C β zeolite from Zeolyst International; calcined before use to obtain its H form) were suspended in 100 kg of distilled water, and the solution was further stirred at 100 rpm for 30 minutes. In a separate container, 24.75 kg of NaAlO2 was dissolved in 399.6 kg of distilled water, and the solution was stirred at 50 rpm for another 30 minutes. The aqueous suspension of seeds was then added to the sodium aluminate solution under stirring, and the empty container was then rinsed with 20 L of distilled water, where the rinse solution was added to the mixture. Then, under stirring at 25 rpm, 555.27 kg of sodium-water glass solution (26 wt% SiO2 and 8 wt% Na2O, obtained from Fa. Woelner) was continuously added to the mixture over 1 hour, and the empty container was then rinsed with 10 L of distilled water, where the rinse solution was then added to the mixture. Then, 96.21 kg of an aqueous solution of colloidal silica (40%; Ludox AS40, available from Grace) was added to the mixture under stirring, and the empty container was then rinsed with 5 L of distilled water, wherein the rinse solution was then added to the mixture.

[0245] The mixture was then heated to 120°C over 3 hours while stirring at 25 rpm, and then crystallized at this temperature for 84 hours. After the reaction mixture was cooled to room temperature, it was filtered, the solid residue was repeatedly washed with distilled water to neutralize, and then dried at 120°C to obtain 122.523 kg of a white crystalline product. Compared with the crystallinity of the seed crystals used in the synthesis, the product showed a crystallinity level of 71% in the 2θ range of 18-25°.

[0246] For Reference Examples 1 and 3, considering that two characteristic reflections were observed in the range of 25-26° 2θ, the XRD of the crystalline product showed an XRD pattern characteristic of a BEA framework structure obtained by organic template-free synthesis.

[0247] Elemental analysis of the crystalline product gave a Si:Al:Na molar ratio of 0.9:0.2:0.2. Thus, the Si:Al molar ratio of the product was 4.5:1.

[0248] The nitrogen isotherm was determined according to DIN 66135, wherein evaluation of the data yielded a value of 643 m / s according to the Langmuir method. 2 / g equivalent surface area and 471m 2 / g of BET surface area.

[0249] Then, 100 g of the crystallized product was added to 1 kg of a 10 wt% aqueous solution of ammonium nitrate, stirred at 80° C. for 2 hours, and then the solid was filtered off and washed with distilled water until the filtrate was free of nitrate. The ion exchange step was then repeated, and the product was subsequently dried at 120° C. overnight to obtain 90 g of an ion-exchanged crystallized product.

[0250] Elemental analysis of the ion exchange product gave a Si:Al:Na molar ratio of 1.17:0.22:0.002. Thus, the Si:Al molar ratio of the product was 5.3:1.

[0251] Reference Example 6: Preparation of zeolite beta by organic template-free synthesis

[0252] 332.1 g NaAlO2 was dissolved in 7578.8 g H2O, followed by the addition of 62.8 g Al-β zeolite seeds (CP814C β zeolite from Zeolyst International; H type), followed by the slow addition of 363.6 g fumed silica ( 200, obtained from Degussa). The mixture was then transferred to a 20 L autoclave and 8062.6 g of sodium-water glass solution (26 wt. % SiO2 and 8 wt. % Na2O, obtained from Fa. Woelner) were slowly added to the mixture while stirring at 200 rpm, wherein a gel was first produced and then dissolved after further addition of solution.

[0253] Then, the mixture was heated to 120°C for 3 hours without stirring, and then crystallized at this temperature for 117 hours. After the reaction mixture was cooled to room temperature, it was filtered, and the solid residue was repeatedly washed with distilled water to neutralize, and then dried at 120°C for 16 hours to obtain 1370 g of a white crystalline product. Compared with the crystallinity of the seed crystals used in the synthesis, the product showed a crystallinity level of 82% in the 2θ range of 18-25°.

[0254] Elemental analysis of the ion exchange product gave a Si:Al:Na molar ratio of 1.07:0.24:0.23. Thus, the Si:Al molar ratio of the product was 4.5:1.

[0255] For Reference Examples 1, 3 and 5, considering the two characteristic reflections observed in the 2θ range of 25-26°, the XRD of the crystalline products showed an XRD pattern characteristic of the BEA framework structure obtained by the organic template-free synthesis method.

[0256] Then, 650 g of the crystallized product was added to 6.5 kg of a 10 wt% aqueous solution of ammonium nitrate, stirred at 80° C. for 2 hours, and then the solid was filtered off and washed with distilled water until the filtrate was free of nitrate. The ion exchange step was then repeated, and the product was subsequently dried at 120° C. for 16 hours. The product was then heated to 450° C. using a heating rate of 1° C. / min, and then calcined at this temperature for 5 hours, thereby obtaining 575 g of a calcined ion exchange crystallized product.

[0257] Elemental analysis of the calcined ion exchange product gave a Si:Al:Na molar ratio of 1.1:0.25:0.004. Thus, the Si:Al molar ratio of the product was 4.4:1.

[0258] The calcined ion exchange product showed a crystallinity level of 86% in the 2θ range of 18-25°, compared to the crystallinity of the seeds used in the initial synthesis.

[0259] Then, 60 g of the calcined ion-exchanged crystalline product was added to 300 g of a 2% HNO3 solution, stirred at 60°C for 2 hours, and then the solid was filtered off and washed with distilled water until the filtrate was free of nitrate. The product was then dried at 120°C for 16 hours, then heated to 450°C at a heating rate of 1°C / min and calcined at this temperature for 5 hours to obtain a white crystalline product.

[0260] Elemental analysis of the final product gave a Si:Al:Na molar ratio of 1.25:0.19:0.01. Thus, the Si:Al molar ratio of the product was 6.6:1.

[0261] The calcined ion exchange product showed a crystallinity level of 52% in the 2θ range of 18-25°, compared to the crystallinity of the seeds used in the initial synthesis.

[0262] Reference Example 7: Dealumination of the β zeolite of Reference Example 6 by acid treatment

[0263] Then, 45 g of the beta zeolite obtained in Reference Example 6 was added to 225 mL of a 2% HNO3 solution, stirred at 60°C for 2 hours, and then the solid was filtered out and washed with distilled water until the filtrate was free of nitrate. The product was then dried at 120°C for 16 hours, then heated to 450°C at a heating rate of 1°C / min and calcined at this temperature for 5 hours, thereby obtaining 44 g of a white crystalline product.

[0264] Elemental analysis of the final product gave a Si:Al:Na molar ratio of 1.35:0.16:0.001. Thus, the Si:Al molar ratio of the product was 8.4:1.

[0265] The calcined ion exchange product showed a crystallinity level of 52% in the 2θ range of 18-25°, compared to the crystallinity of the seeds used in the initial synthesis.

[0266] Reference Example 8: Preparation of zeolite beta by organic template-free synthesis

[0267] 19.91 kg of Al-β zeolite seeds (CP814C β zeolite from Zeolyst International; calcined) were suspended in 100 kg of distilled water, and the solution was further stirred at 100 rpm for 30 minutes. In a separate container, 26.96 kg of NaAlO2 was dissolved in 443.15 kg of distilled water, and the solution was further stirred at 50 rpm for 30 minutes. The aqueous suspension of seeds was then added to the sodium aluminate solution under stirring, and the empty container was then rinsed with 20 L of distilled water, wherein the rinse solution was then added to the mixture. Then, under stirring at 25 rpm, 620.15 kg of sodium-water glass solution (26 wt% SiO2 and 8 wt% Na2O, obtained from Fa. Woelner) was continuously added to the mixture over 1 hour, and the empty container was then rinsed with 10 L of distilled water, wherein the rinse solution was then added to the mixture. Then, 94.78 kg of an aqueous solution of colloidal silica (40%; Ludox AS40, available from Grace) was added to the mixture under stirring, and the empty container was then rinsed with 5 L of distilled water, wherein the rinse solution was then added to the mixture.

[0268] Then, while stirring at 25 rpm, the mixture was heated to 120° C. over 3 hours, and then crystallized at this temperature for 79 hours. After the reaction mixture was cooled to room temperature, it was filtered, the solid residue was repeatedly washed with distilled water to neutralize, and then dried at 120° C., thereby obtaining 117 kg of a white crystalline product. Compared with the crystallinity of the seed crystal used in the synthesis, the product showed a crystallinity level of 72% in the 2θ range of 18-25°.

[0269] For Reference Examples 1, 3, 5 and 6, considering the two characteristic reflections observed in the 2θ range of 25-26°, the XRD of the crystalline products showed an XRD pattern characteristic of the BEA framework structure obtained by organic template-free synthesis.

[0270] Elemental analysis of the product gave a Si:Al:Na molar ratio of 1.07:0.23:0.22. Therefore, the Si:Al molar ratio of the product was 4.7:1.

[0271] The nitrogen isotherm was determined according to DIN 66135, wherein evaluation of the data yielded a value of 611 m / s according to the Langmuir method. 2 / g equivalent surface area.

[0272] Then, 25 kg of the crystallized product was added to 250 kg of a 10 wt% aqueous solution of ammonium nitrate, stirred therein at 80°C for 2 hours, then the solid was filtered off and washed with distilled water until the filtrate was free of nitrates. The ion exchange step was then repeated, and the product was subsequently dried at 120°C for 16 hours. The dried product was then heated to 500°C at a heating rate of 1°C / min and calcined at this temperature for 5 hours. Compared to the crystallinity of the seeds used in the synthesis, the product showed a crystallinity grade of 74% in the 2θ range of 18-25°.

[0273] Elemental analysis of the ion exchange product gave a Si:Al:Na molar ratio of 1.28:0.22:0.001. Thus, the Si:Al molar ratio of the product was 5.8:1.

[0274] The nitrogen isotherm of the ion exchange product was determined according to DIN 66135, wherein evaluation of the data yielded a nitrogen isotherm of 636 m 2 / g equivalent surface area.

[0275] Reference Example 9: Dealumination of the β zeolite of Reference Example 8 by steam and acid treatment

[0276] The product of Reference Example 8 was steamed at 700° C. in a nitrogen atmosphere containing 10% H2O for 1 hour. The steamed material was then subjected to three successive acid treatment steps with a 2% HNO3 solution, in which it was stirred at 60° C. for 2 hours, the solid was then filtered off and washed with distilled water until the filtrate was free of nitrates. The product was then dried at 120° C. for 16 hours, then heated to 450° C. using a ramp rate of 1° C. / min and calcined at this temperature for 5 hours, thereby obtaining a white crystalline product showing a Si:Al molar ratio of 17.9:1.

[0277] Reference Example 10: Synthesis of zeolite beta according to US5824835A

[0278] 513.23 g of colloidal silica (30 wt %, Ludox SM-30), 574.77 g of tetraethylammonium hydroxide (35 wt %), 24.61 g of aluminum hydroxide and 0.68 g of water were added to a container and stirred at 700 rpm for 1 hour. The resulting mixture was transferred to an autoclave and heated to 100 ° C at a rate of 2 ° C / minute. The mixture was stirred at 100 ° C and 60 rpm for 48 hours. The autoclave was cooled to room temperature, opened and 538.9 g of barium hydroxide aqueous solution (5 wt %) was added, followed by 47.94 g of potassium hydroxide aqueous solution (10 wt %). The autoclave was then sealed and the resulting mixture was heated to 150 ° C at a rate of 2 ° C / minute. The mixture was stirred at 150 ° C and 60 rpm for 168 hours. The product was then filtered and dried overnight at 110 ° C.

[0279] The dried zeolitic material was treated with 1 M ammonium chloride adjusted to pH 8 at 60°C for 1 hour. The ion exchange was repeated twice. The product was then collected by centrifugation, washed with water and collected again by centrifugation. The washing / centrifugation was repeated once. The resulting zeolitic material was dried at 110°C for 16 hours. The dried exchanged product was heated to 538°C at 2°C / min in a stream of dry nitrogen and maintained for 3 hours. The temperature was reduced to 250°C and the atmosphere was switched to air, followed by the temperature being raised again to 538°C at 2°C / min and maintained for 3 hours. The resulting calcined material was found to have a crystallinity of 76%, and the product contained a small amount of CHA zeolitic material, as evidenced by XRD (see XRD for Reference Example 10). Figure 6 ).

[0280] Elemental analysis of the ion exchange product gave a Si:Al:K:Ba:C molar ratio of 1:0.123:0.00378:0.0014:0.006. Therefore, the Si:Al molar ratio of the product was 8.1:1.

[0281] Example 1: Alkylation of isobutane with 1-butene

[0282] The catalyst (500mg) of reference examples 2, 4, 5, 7 and 9 was activated at 250°C, then placed in a 100mL Parr reactor, which was immediately closed and purged with nitrogen. As a comparative example, two commercial zeolite samples were used, both of which were obtained by a synthesis method using an organic template, wherein the first showed a Si:Al molar ratio of 12.5 (CP811 obtained from PQ Corporation), and the second showed a Si:Al molar ratio of 30 (H-β obtained from Südchemie). The reactor was cooled on ice, and liquid isobutane was added by cooling at 15°C to ensure that isobutane was in its liquid state with a 31.4mL compressed air-driven plunger. Uncooled 49.1mL plungers were then used to add gaseous 1-butene. The pipeline was then purged with nitrogen to ensure that all olefins were transferred to the reactor. The reaction was carried out at 70-100°C while stirring the slurry. After the reaction was complete, the reactor was cooled on ice and released gas. Subsequently, n-decane was added to the reactor to dilute the reaction product. The reaction was analyzed using a GC-FID instrument with tetradecane as a standard.

[0283] The alkylation of isobutane with 1-butene was tested at an olefin / paraffin ratio of 1 / 50. First, a commercial beta zeolite sample was tested, with the best catalyst providing 149 mg product / g catalyst at 42% C8 selectivity. Figure 4 It can be seen that the beta zeolite with Si / Al ratio of 4.5-5.3 from organic template-free synthesis obtained from Reference Examples 2, 4 and 5 provides significantly higher activity up to 407 mg product / g catalyst compared to the commercial sample obtained from template synthesis. Figure 5 It can be seen that the beta zeolites from the organic template-free synthesis method obtained from Reference Examples 2, 4 and 5 further provide the highest C8 selectivity. Dealumination of the zeolites from the organic template-free synthesis method obtained from Reference Examples 7 and 9 results in lower activity and lower C8 selectivity than the untreated zeolites of Reference Examples 2, 4 and 5.

[0284] from Figure 4 As can be further seen from the results, a clear correlation between the Si:Al ratio and the activity of the zeolite beta catalyst can be observed, wherein the activity decreases with decreasing Si:Al ratio, independently of whether the zeolite is obtained by a template-based or organotemplate-free synthesis, or whether the Si:Al ratio is achieved by subsequent dealumination of the zeolite beta after its synthesis. However, it is quite surprising to find that despite the Figure 5Similar correlations for the C8 selectivity of each catalyst were observed in the results of Reference Examples 2 and 4, but at comparable Si:Al ratios, the beta zeolites obtained from the organic template-free synthesis method showed significantly higher selectivities than the catalysts obtained from the template synthesis method, especially for those samples showing low Si:Al molar ratios. In particular, it was quite unexpectedly found that, compared to the commercial beta zeolite samples obtained from the template synthesis method, which were virtually insensitive to changes in the C8 selectivity, the catalyst samples obtained from the organic template-free synthesis method not only showed significantly higher selectivities, but also showed a strong correlation between the Si:Al molar ratio and the C8 selectivity of the samples. In particular, the samples of Reference Examples 2 and 4 having Si:Al molar ratios of 4-5 gave C8 selectivities that were almost twice as high as those observed for the commercial beta zeolites obtained from the template synthesis method.

[0285] In addition, Reference Example 10, which represents the teaching of the prior art document US Pat. No. 5,824,835 A, was evaluated in the alkylation of isobutane with but-1-ene according to Example 1, and the results are given in Table 1 below, together with the results using the zeolite from the organic template-free synthesis method obtained according to Reference Example 2.

[0286] Table 1: Comparison of the alkylation of isobutane with but-1-ene using the zeolites of Reference Examples 10 and 2

[0287]

[0288] Therefore, it can be seen from the results in Table 1 that the results of the present invention can also be confirmed by the prior art document US5824835A, which specifically teaches the use of β zeolite from conventional (template) synthesis in the alkylation of isobutane with 2-butene. In particular, from the results of the C8 selectivity, it can be seen that the process of the present invention using Reference Example 2 (which is a β zeolite obtained by an organic template-free synthesis method) obtains a much higher selectivity for C8 than that obtained in Reference Example 10, which confirms that Figure 5 The results and general trends shown in .

[0289] Thus, it has surprisingly been found that in a process for the alkylation of isobutane with but-1-ene, the use of a beta zeolite from an organotemplate-free synthesis provides significantly better results in terms of activity and selectivity, particularly in terms of selectivity to C8 paraffin products, than the use of a commercial beta zeolite. Furthermore, it has been quite unexpectedly found that this is not only due to the lower Si:Al molar ratio (which can be provided using an organotemplate-free synthesis), but is further due to the unique structure of the beta zeolite material obtained by the process, particularly in view of the outstanding and completely unexpected selectivity to the desired C8 paraffin products that can be obtained.

[0290] Prior art documents cited:

[0291] -Feller, A. et al., Journal of Catalysis, 2004, Vol. 224, pp. 80-93

[0292] - Dalla Costa, BO et al., Applied Catalysis A2010, 385, pp. 144-152

[0293] -Corma, A. et al., Applied Catalysis A 1994, Vol. 119, pp. 83-96

[0294] - WO2012 / 137133A

[0295] -Xiao et al., Chem. Mater. 2008, 20 , pp. 4533-4535

[0296] - WO2010 / 146156A

[0297] -Majano et al., Chem.Mater.2009, 21 , Vol. 4184-4191

[0298] -US4992616A

[0299] -US5824835A

[0300] -Nivarthy, GS et al., Microporous and Mesoporous Materials 2000, Vol. 35-36, pp. 75-87

[0301] -Nivarthy, G.S. et al., Microporous and Mesoporous Materials 1998, Vol. 22, No. 1-3, pp. 379-388

[0302] -Yuki Kato et al., Journal of the Japan Petroleum Institute 2013, Vol. 56, No. 5, pp. 349-355

Claims

1. A method for alkylating an aliphatic organic compound, comprising: (a) providing a catalyst comprising one or more zeolite materials having a BEA framework structure, wherein the BEA framework structure comprises SiO2 and comprises Al2O3, wherein the one or more zeolite materials are H-type beta zeolite, (b) contacting the catalyst with one or more aliphatic organic compounds in the presence of one or more alkylating agents in one or more reactors to obtain one or more alkylated organic compounds, wherein the one or more alkylating agents include one or more olefins, wherein the olefins include one or more C2-C8 alkenes, wherein the one or more zeolitic materials are obtained by a synthesis process which does not use an organic template as a structure directing agent, wherein in said process the reaction mixture never contains more than 1 wt. % of an organic structure directing agent, based on 100 wt. % of SiO2 contained in the reaction mixture, and wherein beta zeolite seeds are used to crystallize the aluminosilicate gel, wherein the Si:Al molar ratio of the one or more zeolite materials is 3-20, wherein the one or more zeolite materials contain H + as counterions of the framework of the one or more zeolitic materials, wherein the one or more aliphatic organic compounds are one or more branched hydrocarbons having the formula: Where R 1 , R 2 and R 3 are independently of one another an optionally cyclic and / or optionally branched C1-C8-alkyl group.

2. A process according to claim 1, wherein the one or more zeolitic materials are non-calcined.

3. The process according to claim 1, wherein one or more of the one or more zeolite materials has an X-ray diffraction pattern comprising at least the following reflections: Therein 100% relates to the intensity of the largest peak in the X-ray powder diffraction pattern.

4. The method according to claim 3, wherein the X-ray diffraction pattern further comprises the following reflections: 。 5. The process according to any one of claims 1 to 4, wherein the molar ratio of the one or more aliphatic organic compounds to the one or more alkylating agents is from 10 to 250.

6. The process according to any one of claims 1 to 4, wherein the process is carried out in batch or continuous mode.

7. The process according to claim 5, wherein the process is carried out in batch or continuous mode.

Citation Information

Patent Citations

  • Motor operated circuit breakers

    US2870288A

  • Organotemplate-free synthetic process for the production of a zeolitic material

    WO2010146156A1

  • Process for alkylation of organic compounds

    WO2012137133A1

  • Process for alkylation of organic compounds

    CN103717554A

  • Heterogeneous isoparaffin / olefin aklylation process

    US4992616A